SweetScope: An investigation of sweet taste perception in Dutch and UK consumers - Leoné Pretorius; Eva M. Čad; Monica Mars; Janet James; Katherine M. Appleton (Food Quality and Preference, 2026)

Effect of dietary sweet taste exposure on sweet taste liker phenotype, cravings and preferences: secondary outcomes of the Sweet Tooth Trial - Eva M. Čad; Leoné Pretorius; Merel van der Kruijssen; Claudia S. Tang; Hanne BT. de Jong; Monica Mars; Katherine M. Appleton; Kees de Graaf (Appetite, 2026)

Does gender diversity affect the financial efficiency of Spanish Port Authorities? - Daniel Coronado; M. Ángeles Martínez; M. Mar Muñoz (Ocean & Coastal Management, 2026)

Selenium(IV) fate and microbial response in bentonite under high temperature conditions: Towards safe nuclear waste disposal - Mar Morales-Hidalgo; Cristina Povedano-Priego; Marcos F. Martinez-Moreno; Antonio M. Newman-Portela; Pier L. Solari; Fadwa Jroundi; Mohamed L. Merroun (Journal of Environmental Chemical Engineering, 2026)

Orchestrating neuroimaging data processing using the ‘Snakemake’ workflow manager - Damien J. Mannion; Maria del Mar Quiroga; Jacob M. Paul; Marta I. Garrido (Brain Structure and Function, 2026)
The processing of neuroimaging data typically involves a complicated set of operations, which often require different software packages and have intensive computational and storage demands. Although there are many options available for the neuroimaging researcher to establish their preferred set of processing operations, there is relatively little guidance on how to orchestrate such operations within a coherent data processing workflow. Here, by describing the construction of a simplified neuroimaging processing workflow, we demonstrate how the established general-purpose workflow manager ‘Snakemake’ can be used to facilitate neuroimaging data processing. Snakemake allows researchers to use a Python-based markup language to describe how input files are transformed into output files. Snakemake then uses these rules to schedule and execute the computational jobs that are required to generate the output files, without unnecessary recreation of existing output files. This allows the complete processing workflow to be executed with a single command and creates workflows that are interpretable, efficient, and reproducible.

CERES forms a complex with RH37 and eIF4E - Isabel C. Okeke; Alfonso Muñoz; M. Mar Castellano (Plant Cell Reports, 2026)
Key message The translation initiator CERES interacts with the RNA helicase RH37 and bridges the interaction of RH37 with eIF4E.

16S rRNA Gene Sequencing Analysis and Caspase-3 Expression by Propolis Ameliorated Oxaliplatin-Induced Toxicity in Female Rattus norvegicus Pre- and During Pregnancy - Zeinab Kamal; A. A. Ebnalwaled; Dorreia A. M. Zaghloul; Zeinab Al-Amgad; Amany A. Mohamad; Asmaa A. Metwally; Zeinab A. Mar’ie (Biological Trace Element Research, 2026)

Pharmaceuticals, personal care-products and current-use pesticides: a review of the available data from European seas - Víctor M. León; Catherine Munschy; Mário Mil-Homens; María del Mar García-Pimentel; Yann Aminot; Claire Mason; Javier Castro-Jiménez (Environmental Research, 2026)

Effect of aging on the release of additives and the toxicity of microplastics - Alicia Sánchez; Sara Exojo-Trujillo; Diego Ríos; José M. Coll; Mar Masia-Santonja; Dinoraz Vélez; Vicenta Devesa (Environmental Toxicology and Pharmacology, 2026)

Projected Evolution of Climatic Aridity in Spain: Robust Signals and Model Uncertainties - Víctor Trullenque‐Blanco; María del Mar Rondón Velasco; Maialen Iturbide; José Manuel Gutiérrez; Sergio M. Vicente‐Serrano; Santiago Beguería (International Journal of Climatology, 2026)
Spain's geographical position and climate characteristics make it highly vulnerable to climate change–driven projected aridity change. This study assesses the projected evolution of climatic aridity across mainland Spain, the Balearic Islands, and the Canary Islands throughout the 21st century. Using the UNEP Aridity Index ( AI = P / ETo ), we analyse an ensemble of high‐resolution CMIP6 simulations under four Shared Socioeconomic Pathways (SSPs) and four Global Warming Levels (GWLs), relative to the 1985–2014 baseline. The CMIP6 models exhibit a systematic dry bias, characterised by underestimated precipitation ( P ) and overestimated reference evapotranspiration ( ETo ) over the Spanish mainland, leading to artificially low historical AI values and excessively steep ETo trends. To mitigate this bias, we apply a delta‐change ( Δ AI ) method, which corrects the climatological baseline but does not eliminate process‐level uncertainties. Despite these limitations, the ensemble shows a consistent directional signal of increasing aridity across all regions and scenarios. The magnitude of projected aridity change scales with global warming and emissions intensity, reflecting a clear dose–response pattern. This trend is largely attributed to rising ETo , although its physical realism remains uncertain given the models' underestimation of precipitation and the use of empirical models to estimate ETo . Under high‐emission scenarios (SSP3‐7.0 and SSP5‐8.5), arid and semi‐arid zones expand across southern Spain, whilst the Canary Islands experience a pronounced shift towards hyper‐arid conditions. Overall, the results indicate that Spain is likely to face a progressive and spatially heterogeneous increase in climatic aridity, though the mechanistic basis of this change remains uncertain. These findings highlight both the directional robustness of projected aridity change and the need for more physically grounded model evaluation before fully translating these projections into adaptation strategies.

Urban runoff impacts on benthic communities of a receiving stream - Neus Besolí-Mestres; Mar Auró; Sílvia Gómez-Arcusa; Itxaso Martinez-Sanz; M. Isabel Cadena-Aizaga; Núria de Castro-Català; Isabel Muñoz; Mira Petrovic; Sergi Sabater; Anna Freixa (Environmental Pollution, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Mesoscale and submesoscale variability of organic matter in island-induced eddies across their life cycle: implications for the biological carbon pump - J. L. García; J. Arístegui; M. J. Pazó; V. Vieitez dos Santos; N. Hernández-Hernández; Mar Nieto-Cid; M. D. Gelado-Caballero; A. Martínez-Marrero; X. A. Álvarez-Salgado (Frontiers in Marine Science, 2026)
The Canary Islands region exhibits intense mesoscale activity, with eddies generated south the islands by perturbations of the Canary Current. After detachment, these eddies drift southwestward along the Canary Eddy Corridor (CEC), exporting their properties into the open ocean. While mesoscale dynamics in the region are well documented, associated submesoscale structures and their role in the production, transport and remineralization of organic matter remain poorly understood. We investigated meso- and submesoscale variability of dissolved organic carbon (DOC), suspended particulate organic carbon (POCsus), and the chromophoric (CDOM) and fluorescent (FDOM) fractions of dissolved organic matter (DOM), at high spatial resolution across four eddies sampled in 2022. In summer, we studied three newly formed or developing eddies: the cyclonic Garajonay eddy, trapped between La Gomera and El Hierro Islands and sustaining an intense phytoplankton bloom and a developing eddy pair south of Gran Canaria (cyclonic Nublo) and Tenerife (anticyclonic Anaga). In autumn, we sampled Bentayga, a five- month-old anticyclonic intrathermocline eddy drifting along the CEC. Cyclonic eddies showed decreasing DOC, CDOM and protein-like FDOM with age, whereas anticyclonic eddies accumulated humic-like FDOM. At the submesoscale, DOC decreased above the pycnocline and humic-like FDOM below it across the Nublo-Anaga front, while Bentayga exhibited pronounced intra-eddy submesoscale variability in DOC, CDOM, and humic-like FDOM. The residuals of the multiple regression with the thermohaline variables of apparent oxygen utilization (ΔAOU), ΔDOC, ΔPOC, ΔCDOM and ΔFDOM, are independent of water mass mixing and physical motions, and therefore retain the biogeochemical variability associated with local processes. Significant correlations among the residuals of DOC/AOU, CDOM/AOU and FDOM/AOU highlight the central role of DOM in local remineralization, which accounts for up to 68 ± 15% of mesopelagic oxygen demand, resulting in the accumulation of humic-like substances and substantial consumption of chromophoric and protein-like materials. Furthermore, the combined residual relationships of DOC/AOU and POCsus/AOU indicate that up to 88% of mesopelagic oxygen demand in the CEC is driven by local remineralization of DOC and POCsus, suggesting only a minor contribution from sinking POM. Our results demonstrate that meso- and submesoscale processes strongly regulate organic matter transport, remineralization and oxygen consumption in the CEC.

Use of a public questionnaire to evaluate human-wildlife conflict and the efficacy of nonlethal wildlife deterrents: Lessons from a desert city - Alexandra D. Burnett; Matthew M. Mars; Michael T. Bogan; John L. Koprowski (Urban Ecosystems, 2026)
Human-wildlife conflict is a major conservation concern worldwide that is projected to increase in frequency and intensity as urban centers expand. Urban residents can employ a number of nonlethal strategies to deter wildlife from their property and reduce conflict; however, some strategies may be more effective than others. We distributed an online questionnaire to residents in Tucson, Arizona, USA via neighborhood associations to (1) assess attitudes toward and conflict with three focal species: coyote ( Canis latrans ), bobcat ( Lynx rufus ), and collared peccary ( Pecari tajacu ), (2) identify which nonlethal deterrent strategies are most effective for each species, and (3) determine whether habitat fragmentation and degradation influence reported deterrence attempts. Despite the relatively high proportion of general complaints about these three species, we found that respondent attitudes toward each were largely positive. Likewise, a relatively small percentage of respondents reported attempts to deter each species from their property. We found that deterrent techniques used by residents varied in success depending on species, however, low sample sizes prevent a rigorous assessment of each technique’s efficacy. We did not find any relationship between proportion of deterrence attempts in respondent locations and percentage impervious surface cover, distance to nearest riparian corridor, or percentage impervious surface within the riparian corridor. Our results add to previous evidence that nonlethal strategies can be used to reduce human-wildlife conflict and show that such strategies may be successfully employed by urban residents. Our findings further highlight the importance of developing species-specific strategies that conform to the unique ecologies of each species.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Soil microbial carbon consumption is affected by tree and mammal diversity - María LOSADA; Mar SOBRAL; Antonio M. MARTÍNEZ CORTIZAS; Carlos E.P. CERRI; Kristen M. DEANGELIS; Sara VARELA; José M.V. FRAGOSO; Kirsten M. SILVIUS (Pedosphere, 2025)

First record of winter pregnant males of two pipefish species in a Mediterranean coastal lagoon - Adrián Guerrero‐Gómez; Antonio Zamora‐López; Antonio Andrés Herrero‐Reyes; Francisco J. Oliva‐Paterna; Jorge Madrid‐Ruiz; Víctor M. Álvarez‐Navarro; Rocío Peñalver; Mar Torralva (Journal of Fish Biology, 2025)
Syngnathus abaster Risso, 1827 and Syngnathus typhle L., 1758 are key components of fish assemblages in European transitional waters, with well‐documented reproductive cycles typically occurring from spring to autumn. However, recent warming trends in the western Mediterranean has raised questions about potential shifts in their breeding phenology. In January 2025, three pregnant S. abaster males and one S. typhle male were detected in the Mar Menor Coastal lagoon (western Mediterranean), representing the first recorded winter breeding event for both species. The size structure of S. abaster in winter 2025 also contrasted with colder winters, further supporting this interpretation. These findings may reflect a response to recent thermal anomalies and highlight the phenological plasticity of these species. To our knowledge, this is the first indication of potential phenological shifts in syngnathids from transitional waters, with implications for understanding how climate change may influence their reproductive dynamics.

A CNN Autoencoder for Learning Latent Disc Geometry from Segmented Lumbar Spine MRI - Mattia Perrone; D’Mar M. Moore; Daisuke Ukeba; John T. Martin (Annals of Biomedical Engineering, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

Corrigendum to “Examining the influence of corruption on port efficiency in West Africa and the Mid-Atlantic: A Bootstrapped DEA analysis” [Ocean. Coast. Manag. 269, October (2025), 107813] - Andrea Rodríguez; Antonio Gil Ropero; M. Mar Cerban; Lourdes Trujillo (Ocean & Coastal Management, 2025)

Examining the influence of corruption on port efficiency in West Africa and the Mid-Atlantic: A bootstrapped DEA analysis - Andrea Rodríguez; Antonio Gil Ropero; M. Mar Cerban; Lourdes Trujillo (Ocean & Coastal Management, 2025)

Sea temperature shapes differences in European sardine (Sardina pilchardus) growth in two adjacent areas in the NW Mediterranean Sea - Joan Mir-Arguimbau; Paloma Martín; Marc Balcells; Jordi Salat; M. Mar Flexas; Nuria Raventós; Ana Sabatés (Marine Environmental Research, 2025)

Determination of Toxic Tropane Alkaloids in Globally Sourced Soya, Cereals and Products Using Dilute-and-Shoot Technique Coupled with LC-MS/MS - Rufielyn S. Gravador; Brett Greer; Simon A. Haughey; M. Mar Aparicio-Muriana; Wilfred A. Abia; Alexandra-Irina Mavrochefalos; Anne P. Nugent; Christopher T. Elliott (Exposure and Health, 2025)
For the first time, this study reports the content of tropane alkaloids (TAs) in soybean and soymeal samples sourced from 13 different countries, as well as in various cereals (including corn, millet, wheat, and sorghum) and a product (Super Cereals). The analysis was conducted using a fully validated solid-liquid extraction (SLE) with dilute-and-shoot (DnS) method along with a liquid chromatography-tandem mass spectrometry (LC-MS/MS) triple quadrupole system. The samples were extracted using a solution of acetonitrile and water (60:40) with 1% formic acid. The limits of quantification (LOQ) were 0.10 µg kg −1 and 0.25 µg kg −1 for atropine and scopolamine, respectively. The extraction recovery was at least 80%, and the intra- and inter-day precision (relative standard deviation) were below 15% at 1, 5, and 50 µg kg −1 atropine and scopolamine spiked levels. The validation parameters showed that the method was fit for the purpose of accurate LC-MS/MS quantification of atropine and scopolamine. The SLE with DnS is high-throughput, enabling the extraction of TAs in 2.3 min per sample or at least 60 samples in 140 min. Whereas typical TA extraction methods require lengthy and costly clean-up and concentration steps, the DnS does not require these steps, sophisticated equipment, or an expert operator for execution, which makes it a simpler and straightforward procedure for TA analysis in different grain-based food matrices. Application of the LC-MS/MS method showed that one in 80 millet or corn, 18 in 269 soybeans, 20 in 62 soymeal and 20 in 42 Super Cereals samples had atropine and scopolamine above the maximum level of 1 μg kg −1 set by the EU Commission Regulation. TA contamination in these samples could either be due to the mixing with (visible) or exposure to (invisible) TA-producing plant material. The latter was proven through an exposure experiment, which showed that atropine and scopolamine from Datura stramonium seeds can be transferred to food grains (soybeans) invisibly with prolonged contact.

Global Warming and the Spread of the Introduced Jellyfish Cassiopea andromeda : Thermal Niche and Habitat Suitability in the Mediterranean Sea - Lara M. Fumarola; Valentina Leoni; Guillaume Marchessaux; Gianluca Sarà; Stefano Piraino; Mar Bosch‐Belmar (Global Change Biology, 2025)
Climate change affects marine ecosystems in multiple ways, including sea warming and changes in biological community structure and diversity. The Mediterranean Sea has emerged as one of the most vulnerable regions, also because of the diverse patterns of introduction of non‐native species. First recorded in the coastal waters of Cyprus in 1903, the Red Sea jellyfish Cassiopea andromeda (Forskål, 1775) is spreading its distribution and local abundance, posing questions on its potential ecological implications. Here we identified the thermal tolerance, habitat suitability, and potential distribution range of the C. andromeda polyps, a key life cycle stage responsible for asexual reproduction and population persistence. By laboratory‐controlled respirometric measurements, we assessed that the polyps of C. andromeda exhibit their optimal metabolic performances at high water temperatures, but they are tolerant to winter conditions across the Mediterranean basin. Combining experimental respiration measurements with modelling approaches enabled the definition of the species' fundamental thermal niche, with an optimal seawater temperature at 35.7°C and critical limits at 6.4°C (minimum) and 39°C (maximum). Trait‐based thermal habitat suitability maps indicated a future increase of favourable habitats for the species under warming conditions according to the Representative Concentration Pathways (RCP 4.5 and 8.5 for 2050) in Mediterranean coastal areas. In the context of climate change scenarios, the rise of seawater temperature may enable polyps to thrive across a wider geographic range, predicting a westward and northward enlargement of C. andromeda populations in the Mediterranean Sea.

Spatial patterns and characterization of marine litter from sandy beaches facing an urban area and a Marine Protected Area - Laura Corbari; Manuel Berlino; Ana Milivojevic; Ana Maria Botero Angel; Mar Bosch-Belmar; Fulvio Capodici; Giuseppe Ciraolo; Gianluca Sarà; M. Cristina Mangano (Frontiers in Marine Science, 2025)
Marine litter is a globally recognized issue that impacts the environment and has significant negative effects on both human health and socio-economic activities. Mainly composed of plastic items, marine litter can be dispersed in the ocean by surface currents, sink to the seafloor, and/or be deposited on coastal areas. Monitoring, quantifying, and characterizing beach litter can be time-consuming but can be conducted using established monitoring protocols (both European and international) and supported by citizen science. Here, we present and discuss the main outcomes from in situ monitoring campaigns covering sandy beaches in both an urban area and a Marine Protected Area. Both macro- and meso-litter were quantified and identified by material, size, shape, and color. The quantity and heterogeneity of items (classified using the Joint List of Litter Categories for Macrolitter Monitoring) were highest in areas with the greatest user presence (e.g., refreshment areas, shops, and restaurants). Free-access beaches showed the highest density of macro-litter items compared to beaches where entrance was regulated by three levels of subscription. Artificial polymers/plastics, particularly plastic caps and lids, dominated, followed by paper and cardboard fragments. A database has been created allowing to highlight hotspots and patterns of occurrence that can inform local management measures, urging municipalities to improve waste management.

Three independent measures of sweet taste liking have weak and inconsistent associations with sugar and sweet food intake - insights from the sweet tooth study - Eva M. Čad; Merel van der Kruijssen; Claudia S. Tang; Leoné Pretorius; Hanne B.T. de Jong; Monica Mars; Katherine M. Appleton; Kees de Graaf (Food Quality and Preference, 2025)

Disentangling upwelling: how light and nutrient supply shape primary producers and stoichiometry in the Humboldt upwelling system - Antonia U. Thielecke; Mar Fernández-Méndez; Javier Arístegui; Moritz Baumann; Jacqueline Behncke; Stella A. Berger; Veit Dausmann; Silvia Georgieva; Silvan U. Goldenberg; Gonzalo V. Gomez-Saez; Michelle Graco; Toralf Heene; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Beyond borders: The role of protected areas in promoting bat-mediated pest suppression in rural areas of Madagascar - Carme Tuneu-Corral; Chatain Andrianalijaona; Fabrice Davy Benirina; Steven M. Goodman; Vanessa A. Mata; Michaël Luciano Tantely; Mar Cabeza; Cecilia Montauban; David López-Bosch; Adrià López-Baucells (Agriculture, Ecosystems & Environment, 2025)

Microbial colonization and function of biofilms developing on plastics and bioplastics in a pristine mountain stream ecosystem - Mar Oliva‐Albert; Alba Bellostas‐Carreras; José Luis Guijosa‐Ortega; Anna Doménech‐Pascual; Judit Boadella; Joan Pere Casas‐Ruiz; David Pineda‐Morante; Yoann Menard; Laura Ayuso; Anna Lupon; Eugènia Martí; Helena Guasch; et al. (Limnology and Oceanography, 2025)
Streams naturally receive allochthonous particulate organic materials, but human activity may contribute additional plastic litter inputs, which can affect ecosystem functioning. Our objective was to assess the effect of plastic and bioplastic inputs on microbial biomass and function in a pristine mountain stream. To do that, fragments of plastics (polyethylene—PE, polypropylene—PP), bioplastics (polyhydroxyalkanoate—PHA, polylactic acid—PLA), and wood (as a natural material) were immersed in the stream and collected after 120, 202, 316, and 383 d. Fungal, prokaryotic, and algal biomass, and autotrophic and heterotrophic functions (net primary production, extracellular enzyme activities, and nutrient uptake) were analyzed together with organic matter weight changes over time. Wood showed high fungal and prokaryotic biomass, phosphatase and β‐glucosidase activities, and a significant weight loss, as related to the degradation process. In contrast, plastics and bioplastics did not lose weight and were mainly colonized by algae, suggesting that they serve as an inert surface and over‐enhance primary production. However, phenol oxidase (ligninolytic enzyme) activity in plastics and bioplastics was similar to that in wood and increased with time together with heterotrophic biomass. This indicates that plastispheres can contribute to the degradation of plastics and bioplastics, which may become a carbon source in the long term. Overall, the observed dynamics of microbial biomass and metabolism in the plastispheres point to their potential effect on stream nutrient and carbon cycles. The study highlights the need for careful human activities in pristine mountain watersheds to avoid altering their ecosystem functioning.

Dietary vitamin D intake and 2-year changes in cognitive function in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Jiaqi Ni; Indira Paz-Graniel; Estefanía Toledo; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (GeroScience, 2025)
The protective role of dietary vitamin D intake on cognitive function is of interest, but evidence remains inconsistent. We aimed to evaluate the association between dietary vitamin D intake and 2-year cognitive changes in older adults at risk of cognitive decline. This longitudinal study comprised 5454 individuals (aged 55–75 years in men and 60–75 years in women) who exhibited overweight/obesity and metabolic syndrome. Data on dietary vitamin D intake was assessed using a validated 143-item food frequency questionnaire. Cognitive function was assessed through five composite scores derived from a comprehensive battery of eight neuropsychological tests, encompassing global cognitive function, general cognitive function, attention, executive function, and language domains. Multivariable-adjusted linear regression models were fitted to examine the association between energy-adjusted cumulative average dietary vitamin D intake over time and 2-year changes in cognitive function. After adjusting for multiple covariates, energy-adjusted cumulative average dietary vitamin D intake as a continuous variable was associated with greater 2-year improvements in global cognitive function ( β 1.18 × 10 −2 ; 95% CI 0.19 × 10 −2 to 2.17 × 10 −2 ), executive function ( β 1.12 × 10 −2 ; 95% CI 0.03 × 10 −2 to 2.21 × 10 −2 ), and language ( β 1.61 × 10 −2 ; 95% CI 0.43 × 10 −2 to 2.78 × 10 −2 ). Additionally, the higher cumulative average dietary vitamin D intake quartile was associated with an increase in global cognitive function ( β 7.10 × 10 −2 ; 95% CI 0.59 × 10 −2 to 13.6 × 10 −2 ), language ( β 7.07 × 10 −2 ; 95% CI − 0.52 × 10 −2 to 14.7 × 10 −2 ), and a lower decline in attention ( β 9.58 × 10 −2 ; 95% CI 1.60 × 10 −2 to 17.5 × 10 −2 ). A higher dietary vitamin D intake was associated with modest favorable changes in cognitive function and a reduced cognitive decline over a 2-year period. These findings highlight the need for further research to explore the potential benefits of boosting dietary vitamin D intake for cognitive health in older adults.

Effects of climate on leaf phenolics, insect herbivory, and their relationship in pedunculate oak (Quercus robur) across its geographic range in Europe - Elena Valdés-Correcher; Yasmine Kadiri; Audrey Bourdin; Anna Mrazova; Flavius Bălăcenoiu; Manuela Branco; Michal Bogdziewicz; Mona Chor Bjørn; Thomas Damestoy; Jovan Dobrosavljević; Maria Faticov; Sofia Gripenberg; et al. (Oecologia, 2025)
An increase in biotic interactions towards lower latitudes is one of the most consistent patterns in ecology. Higher temperatures and more stable climatic conditions at low latitudes are thought to enhance biotic interactions, accelerating biological evolution and leading to stronger anti-herbivore defences in plants. However, some studies report contradictory findings, highlighting the need for further investigation into the underlying mechanisms. We used a combination of field observations and feeding trials in controlled environments to investigate the effect of climate on chemical defences and insect herbivory in pedunculate oak ( Quercus robur L.) throughout most of its geographic range in Europe, while controlling for physical defences. The concentration of lignin, flavonoids, and total phenolics increased significantly with temperature, whereas both field herbivory and weight of spongy moth ( Lymantria dispar L.) larvae were negatively influenced by temperature. Lignin concentration positively influenced the weight of spongy moth larvae whereas it had no effect on field herbivory. We found no evidence of strong positive relationships between insect herbivory and larvae growth with leaf defences. Our study underscores the complexity of plant–herbivore interactions along climatic gradients and highlights the need for further research to disentangle these intricate relationships.

Novel CRISPR-Cas9 iPSC knockouts for PCCA and PCCB genes: advancing propionic acidemia research - Emilio M. García-Tenorio; Mar Álvarez; Mónica Gallego-Bonhomme; Lourdes R. Desviat; Eva Richard (Human Cell, 2025)
Propionic acidemia (PA) is a rare autosomal recessive metabolic disorder caused by mutations in the PCCA and PCCB genes, which encode subunits of the mitochondrial enzyme propionyl-CoA carboxylase (PCC). This enzyme deficiency leads to the accumulation of toxic metabolites, resulting in severe metabolic dysfunction. To create ideal in vitro disease models of PA with isogenic controls and provide a robust platform for therapeutic research, we generated two induced pluripotent stem cell (iPSC) lines with knockout (KO) mutations in the PCCA and PCCB genes using CRISPR-Cas9 gene editing in a healthy control iPSC line. The KO iPS cells were successfully established and characterized, confirming the presence of frameshift insertions and deletions in each target gene, as well as the loss of the corresponding transcript, protein expression, and activity. Additionally, the generated iPSC lines exhibit hallmark characteristics of pluripotency, including the potential to differentiate into all three germ layers. Our PCCA and PCCB KO iPSC models provide a valuable tool for studying the molecular mechanisms underlying PA and hold potential for advancing new therapeutic approaches.

Analytical approaches to track nylon 6 microplastic fiber degradation using HKUST-1(Cu/Fe)-derived CuO/TiO2 photocatalyst - Ángel Eduardo Rodríguez-Olivares; Jorge Luis Guzmán-Mar; Pedro César Quero-Jiménez; Sagrario M. Montemayor; Lourdes Maya-Treviño; Laura Hinojosa-Reyes (Journal of Water Process Engineering, 2025)

Green extraction strategies to obtain bioactive compounds from ‘Charelo’ vine shoots - Camila C. Muñoz-Realpe; María del Mar Contreras; Alfonso M. Vidal; Eulogio Castro; Inmaculada Romero (Sustainable Chemistry and Pharmacy, 2025)

Geopolitical and competition analysis: The case of Western African ports and the port of Las Palmas in the mid-Atlantic European Islands - Andrea Rodríguez; M. Mar Cerbán; Lourdes Trujillo (Journal of Transport Geography, 2025)

Flexural behaviour of functionally graded reinforced concrete slabs with vertical or horizontal layers - Mar Giménez Fernández; Janet M. Lees (Engineering Structures, 2025)

Understanding stakeholders' perception on developing seagrass-associated tourism: Evidence from marine protected areas of Bintan Island, Indonesia - Husen Rifai; Kevin Muhamad Lukman; Jay Mar D. Quevedo; Prue Francis; Nurul Dhewani M. Sjafrie; Triyono; Len Mckenzie; Rahman Hidayat; Aditya Hikmat Nugraha; Tri Edi Kuriandewa; Siti Hajar Suryawati; Bayu Prayudha; et al. (Marine Pollution Bulletin, 2024)

Chromosome-Y haplogroups in Asturias (Northern Spain) and their association with severe COVID-19 - Mar González-Fernández; Daniel Vázquez-Coto; Guillermo M. Albaiceta; Laura Amado-Rodríguez; Marta G. Clemente; Lucinda Velázquez-Cuervo; Claudia García-Lago; Juan Gómez; Eliecer Coto (Molecular Genetics and Genomics, 2024)
The main objective of this study was to determine whether the common Y-haplogroups were be associated with the risk of developing severe COVID-19 in Spanish male. We studied 479 patients who required hospitalization due to COVID-19 and 285 population controls from the region of Asturias (northern Spain), They were genotyped for several polymorphisms that define the common European Y-haplogroups. We compared the frequencies between patients and controls aged ≤ 65 and >65 years. There were no different haplogroup frequencies between the two age groups of controls. Haplogroup R1b was less common in patients aged ≤65 years. Haplogroup I was more common in the two patient´s groups compared to controls ( p = 0.02). Haplogroup R1b was significantly more frequent among hypertensive patients, without difference between the hypertensive and normotensive controls. This suggested that R1b could increase the risk for severe COVID-19 among male with pre-existing hypertension. In conclusion, we described the Y-haplogroup structure among Asturians. We found an increased risk of severe COVID-19 among haplogroup I carriers, and a significantly higher frequency of R1b among hypertensive patients. These results indicate that Y-chromosome variants could serve as markers to define the risk of developing a severe form of COVID-19.

Dynamics of peripheral T cell exhaustion and monocyte subpopulations in neurocognitive impairment and brain atrophy in chronic HIV infection - Brooks I. Mitchell; Isabelle E. Yazel Eiser; Kalpana J. Kallianpur; Louie Mar Gangcuangco; Dominic C. Chow; Lishomwa C. Ndhlovu; Robert Paul; Cecilia M. Shikuma (Journal of NeuroVirology, 2024)
Background HIV-associated neurocognitive disorders (HAND) is hypothesized to be a result of myeloid cell-induced neuro-inflammation in the central nervous system that may be initiated in the periphery, but the contribution of peripheral T cells in HAND pathogenesis remains poorly understood. Methods We assessed markers of T cell activation (HLA-DR + CD38+), immunosenescence (CD57 + CD28-), and immune-exhaustion (TIM-3, PD-1 and TIGIT) as well as monocyte subsets (classical, intermediate, and non-classical) by flow cytometry in peripheral blood derived from individuals with HIV on long-term stable anti-retroviral therapy (ART). Additionally, normalized neuropsychological (NP) composite test z-scores were obtained and regional brain volumes were assessed by magnetic resonance imaging (MRI). Relationships between proportions of immune phenotypes (of T-cells and monocytes), NP z-scores, and brain volumes were analyzed using Pearson correlations and multiple linear regression models. Results Of N = 51 participants, 84.3% were male, 86.3% had undetectable HIV RNA < 50 copies/ml, median age was 52 [47, 57] years and median CD4 T cell count was 479 [376, 717] cells/uL. Higher CD4 T cells expressing PD-1 + and/or TIM-3 + were associated with lower executive function and working memory and higher CD8 T cells expressing PD-1 + and/or TIM-3 + were associated with reduced brain volumes in multiple regions (putamen, nucleus accumbens, cerebellar cortex, and subcortical gray matter). Furthermore, higher single or dual frequencies of PD-1 + and TIM-3 + expressing CD4 and CD8 T-cells correlated with higher CD16 + monocyte numbers. Conclusions This study reinforces evidence that T cells, particularly those with immune exhaustion phenotypes, are associated with neurocognitive impairment and brain atrophy in people living with HIV on ART. Relationships revealed between T-cell immune exhaustion and inflammatory in CD16 + monocytes uncover interrelated cellular processes likely involved in the immunopathogenesis of HAND.

Flowering seasonality and airborne pollen recent trends in Sierra de las Nieves, the southernmost National Park in continental Spain - Enrique de Gálvez-Montañez; M. Mar Trigo; Marta Recio; Antonio Picornell (Agricultural and Forest Meteorology, 2024)

Heterogeneity of nitrogen fixation in the mesopelagic zone of the South China Sea - Siqi Wu; Xianhui Sean Wan; Moge Du; Xirong Chen; Corday R. Selden; Mar Benavides; Sophie Bonnet; Carolin R. Löscher; M. Robert Hamersley; Margaret R. Mulholland; Xiuli Yan; Shuh-Ji Kao (Frontiers in Marine Science, 2024)
Biological dinitrogen (N 2 ) fixation, the energetically expensive conversion of N 2 gas to ammonia, plays an essential role in balancing the nitrogen budget in the ocean. Accumulating studies show detectable N 2 fixation rates below the euphotic zone in various marine systems, revealing new insights of marine N 2 fixation. However, the reported rates are highly variable and frequently fall close to detection limits, raising the question of the ubiquity and significance of N 2 fixation in the global dark ocean. Using highly sensitive isotopic labeling incubation including a set of control incubations, we confirm the occurrence of mesopelagic N 2 fixation in the South China Sea. Interestingly, we consistently observed that ca. 30% of samples show a significant elevation of 15 N in the particulate nitrogen after incubation at most depths (200 - 1000 m). Although this approach does not allow accurate quantification of N 2 fixation rates, our data suggest the occurrence of dark N 2 fixation yet with highly heterogeneous signals in the mesopelagic zone of the South China Sea. A data compilation of reported N 2 fixation in the global dark ocean further reveals that such heterogeneity has also been observed elsewhere, unveiling the ubiquitous heterogeneity in mesopelagic N 2 fixation. Thus, we call for more observations to constrain mesopelagic N 2 fixation budgets and to understand the underlying mechanism for such heterogeneity.

Traces of the past: assessing the impact of potentially toxic elements from an abandoned mine on groundwater and agricultural soil in San Luis Potosí, México - M. Silva-Gigante; L. Hinojosa-Reyes; M. Bazzan-Dessuy; J. M. Rosas-Castor; D. E. Torres-Gaytán; P. C. Quero-Jiménez; A. Caballero-Quintero; J. L. Guzmán-Mar (Environmental Monitoring and Assessment, 2024)

Estimating black carbon levels using machine learning models in high-concentration regions - Pratima Gupta; Pau Ferrer-Cid; Jose M. Barcelo-Ordinas; Jorge Garcia-Vidal; Vijay Kumar Soni; Mira L. Pöhlker; Ajit Ahlawat; Mar Viana (Science of The Total Environment, 2024)

Omics biomarkers and an approach for their practical implementation to delineate health status for personalized nutrition strategies - Jaap Keijer; Xavier Escoté; Sebastià Galmés; Andreu Palou-March; Francisca Serra; Mona Adnan Aldubayan; Kristina Pigsborg; Faidon Magkos; Ella J. Baker; Philip C. Calder; Joanna Góralska; Urszula Razny; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Exploring Genetic Variations Among Palestinian Watermelon (Citrullus lanatus) Germplasm Using RAPD Molecular Markers - Yamen A. S. Hamdan; Abdalmenem I. M. Hawamda; Laith badran; Estabraq Daraghmeh; Linda Mar’i; Anas Khalaf; Ramiz Maraabeh; Raghda Ibrahim; R. Basheer-Salimia; Mazen Salman (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Integrating brain function and structure in the study of the human attentional networks: a functionnectome study - Mar Martín-Signes; Pedro M. Paz-Alonso; Michel Thiebaut de Schotten; Ana B. Chica (Brain Structure and Function, 2024)
Attention is a heterogeneous function theoretically divided into different systems. While functional magnetic resonance imaging (fMRI) has extensively characterized their functioning, the role of white matter in cognitive function has gained recent interest due to diffusion-weighted imaging advancements. However, most evidence relies on correlations between white matter properties and behavioral or cognitive measures. This study used a new method that combines the signal from distant voxels of fMRI images using the probability of structural connection given by high-resolution normative tractography. We analyzed three fMRI datasets with a visual perceptual task and three attentional manipulations: phasic alerting, spatial orienting, and executive attention. The phasic alerting network engaged temporal areas and their communication with frontal and parietal regions, with left hemisphere dominance. The orienting network involved bilateral fronto-parietal and midline regions communicating by association tracts and interhemispheric fibers. The executive attention network engaged a broad set of brain regions and white matter tracts connecting them, with a particular involvement of frontal areas and their connections with the rest of the brain. These results partially confirm and extend previous knowledge on the neural substrates of the attentional system, offering a more comprehensive understanding through the integration of structure and function.

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

Amino-modified upcycled biochar achieves selective chromium removal in complex aqueous matrices - Kenneth Flores; Diego F. Gonzalez; Helia M. Morales; Arnulfo Mar; Sergi Garcia-Segura; Jorge L. Gardea-Torresdey; Jason G. Parsons (Journal of Environmental Management, 2024)

Preparation and release of antibacterial Na-mica-4/chlorhexidine nanocomposites - Luís H. Oliveira; Idglan S. de Lima; Denise B. França; Alan I.S. Moraes; Maria G. Fonseca; Humberto M. Barreto; Santiago Medina-Carrasco; Josy A. Osajima; Edson C. da Silva-Filho; María del Mar Orta (Applied Clay Science, 2024)

New macrofossil evidence detail the Holocene vegetation of the Iberian Central System - Salvia García-Álvarez; Mar Génova; Ignacio García-Amorena; Carlos Morla; Sergio Rastrero; José M. Postigo-Mijarra (Review of Palaeobotany and Palynology, 2024)

A multi-framework analysis of stakeholders’ perceptions in developing a localized blue carbon ecosystems strategy in Eastern Samar, Philippines - Jay Mar D. Quevedo; Charissa M. Ferrera; Marie Grace Pamela G. Faylona; Ryo Kohsaka (Ambio, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Specificities and commonalities of the Planctomycetes plasmidome - María del Mar Quiñonero‐Coronel; Damien Paul Devos; M. Pilar Garcillán‐Barcia (Environmental Microbiology, 2024)
Plasmids, despite their critical role in antibiotic resistance and modern biotechnology, are understood in only a few bacterial groups in terms of their natural ecological dynamics. The bacterial phylum Planctomycetes, known for its unique molecular and cellular biology, has a largely unexplored plasmidome. This study offers a thorough exploration of the diversity of natural plasmids within Planctomycetes, which could serve as a foundation for developing various genetic research tools for this phylum. Planctomycetes plasmids encode a broad range of biological functions and appear to have coevolved significantly with their host chromosomes, sharing many homologues. Recent transfer events of insertion sequences between cohabiting chromosomes and plasmids were also observed. Interestingly, 64% of plasmid genes are distantly related to either chromosomally encoded genes or have homologues in plasmids from other bacterial groups. The planctomycetal plasmidome is composed of 36% exclusive proteins. Most planctomycetal plasmids encode a replication initiation protein from the Replication Protein A family near a putative iteron‐containing replication origin, as well as active type I partition systems. The identification of one conjugative and three mobilizable plasmids suggests the occurrence of horizontal gene transfer via conjugation within this phylum. This comprehensive description enhances our understanding of the plasmidome of Planctomycetes and its potential implications in antibiotic resistance and biotechnology.

Global wild rice germplasm resources conservation alliance: World Wild-Rice Wiring - Xiaoming Zheng; Disna Ratnasekera; Jiayu Fan; Robert J. Henry; Beng-Kah Song; Kenneth M. Olsen; Bal Krishna Joshi; Maria Celeste N. Banaticla-Hilario; Tonapha Pusadee; Adane Getachew Melaku; Yêyinou Laura Estelle Loko; Koukham Vilayheuang; et al. (Molecular Plant, 2024)

Associations between attitudes towards and reported intakes of sugars, low/no-calorie sweeteners, and sweet-tasting foods in a UK sample - Claudia S. Tang; Monica Mars; Janet James; Katherine M. Appleton (Appetite, 2024)

Sustainable vine shoots-to-ethanol valorisation by a sequential acid/organosolv pretreatment - Diego Cardoza; María del Mar Contreras; Marta Lara-Serrano; Silvia Morales-delaRosa; Jose M. Campos-Martín; Inmaculada Romero; Eulogio Castro (Process Safety and Environmental Protection, 2024)

Antimalarial Drug Combination Predictions Using the Machine Learning Synergy Predictor (MLSyPred©) tool - Abiel Roche-Lima; Angélica M. Rosado-Quiñones; Roberto A. Feliu-Maldonado; María Del Mar Figueroa-Gispert; Jennifer Díaz-Rivera; Roberto G. Díaz-González; Kelvin Carrasquillo-Carrion; Brenda G. Nieves; Emilee E. Colón-Lorenzo; Adelfa E. Serrano (Acta Parasitologica, 2024)
Purpose Antimalarial drug resistance is a global public health problem that leads to treatment failure. Synergistic drug combinations can improve treatment outcomes and delay the development of drug resistance. Here, we describe the implementation of a freely available computational tool, Machine Learning Synergy Predictor (MLSyPred©), to predict potential synergy in antimalarial drug combinations. Methods The MLSyPred© synergy prediction method extracts molecular fingerprints from the drugs’ biochemical structures to use as features and also cleans and prepares the raw data. Five machine learning algorithms (Logistic Regression, Random Forest, Support vector machine, Ada Boost, and Gradient Boost) were implemented to build prediction models. Implementation and application of the MLSyPred© tool were tested using datasets from 1540 combinations of 79 drugs and compounds biologically evaluated in pairs for three strains of Plasmodium falciparum (3D7, HB3, and Dd2). Results The best prediction models were obtained using Logistic Regression for antimalarials with the strains Dd2 and HB3 (0.81 and 0.70 AUC, respectively) and Random Forest for antimalarials with 3D7 (0.69 AUC). The MLSyPred© tool yielded 45% precision for synergistically predicted antimalarial drug combinations that were annotated and biologically validated, thus confirming the functionality and applicability of the tool. Conclusion The MLSyPred© tool is freely available and represents a promising strategy for discovering potential synergistic drug combinations for further development as novel antimalarial therapies.

Pollen recognition through an open-source web-based system: automated particle counting for aerobiological analysis - Antonio Jesús Chaves; Cristian Martín; Luis Llopis Torres; Manuel Díaz; Rocío Ruiz-Mata; Enrique de Gálvez-Montañez; Marta Recio; M. Mar Trigo; Antonio Picornell (Earth Science Informatics, 2024)
Airborne pollen is produced by plants for their sexual reproduction and can have negative impacts on public health. The current monitoring systems are based on manual sampling processes which are tedious and time-consuming. Due to that, pollen concentrations are often reported with a delay of up to one week. In this study, we present an open-source user-friendly web application powered by deep learning for automatic pollen count and classification. The application aims to simplify the process for non-IT users to count and classify different types of pollen, reducing the effort required compared to manual methods. To overcome the challenges of acquiring large labelled datasets, we propose a semi-automatic labelling approach, which combines human expertise and machine learning techniques. The results demonstrate that our approach significantly reduces the effort required for users to count and classify pollen taxa accurately. The model achieved high precision and recall rates ( $$\varvec{>96%}$$ > 96 % mAP@0.5), enabling reliable pollen identification and prediction.

Effects of climate change on Platanus flowering in Western Mediterranean cities: Current trends and future projections - Antonio Picornell; José M. Maya-Manzano; Marta Fernández-Ramos; Juan J. Hidalgo-Barquero; Raúl Pecero-Casimiro; Rocío Ruiz-Mata; Enrique de Gálvez-Montañez; María del Mar Trigo; Marta Recio; Santiago Fernández-Rodríguez (Science of The Total Environment, 2024)

From small waterbodies to large multi-service providers: Assessing their ecological multifunctionality for terrestrial birds in Mediterranean agroecosystems - José M. Zamora-Marín; Antonio Zamora-López; Francisco J. Oliva-Paterna; Mar Torralva; María Mar Sánchez-Montoya; José F. Calvo (Agriculture, Ecosystems & Environment, 2024)

An optimized electro-fenton pretreatment for the degradation and mineralization of a mixture of ofloxacin, norfloxacin, and ciprofloxacin - I.A. Larralde-Piña; K. Acuña-Askar; M. Villanueva-Rodríguez; J.L. Guzmán-Mar; J.C. Murillo-Sierra; E.J. Ruiz-Ruiz (Chemosphere, 2023)

Long-term bathymetric changes in the submerged delta of the Turia river since the nineteenth century (Western Mediterranean) and their drivers - Rafael Garcés; Mar Roca; Borja Martínez-Clavel; Ana M. Blázquez (Science of The Total Environment, 2023)

A review and meta-analysis of the environmental biology of bleak Alburnus alburnus in its native and introduced ranges, with reflections on its invasiveness - Dani Latorre; Guillem Masó; Carlos Cano-Barbacil; José M. Zamora-Marin; David Almeida; Lorenzo Vilizzi; J. Robert Britton; Alejandra Cruz; Carlos Fernández-Delgado; Anni G. González-Rojas; Rafael Miranda; Francesc Rubio-Gracia; et al. (Reviews in Fish Biology and Fisheries, 2023)
The bleak Alburnus alburnus is a medium body-size leuciscid fish that is naturally distributed across central European and western Asian fresh waters. However, during the last two decades A. alburnus has been widely introduced elsewhere in Europe and in northern Africa, mostly as a forage species for game fishes. Given its relatively recent history of invasion in non-native Eurasian waters, where it can become highly abundant, A. alburnus poses a serious risk to native communities where introduced. This study provides a review and meta-analysis of the biological traits of A. alburnus coupled with insights into its invasiveness. In its native range, A. alburnus has a moderate lifespan, inhabiting lakes or still waters in medium-to-large rivers, where it feeds mainly on zooplankton. However, non-native A. alburnus populations display high phenotypic plasticity in their biological attributes. Thus, growth, reproductive and/or dietary traits have adapted to local environmental conditions, with the species also invading lotic (stream) ecosystems. Feeding changes to benthic invertebrates, plant material and detritus when zooplankton is scarce. Such plasticity, including broad physiological tolerance, is likely to facilitate the species' adaptation and invasion of new habitats in the near future.

Associations between attitudes towards and intakes of sweet-tasting foods, sugar, and sweeteners in the United Kingdom - Claudia S. Tang; Monica Mars; Janet James; Katherine M. Appleton (Appetite, 2023)

Solar photocatalytic degradation of polyethylene terephthalate nanoplastics: Evaluation of the applicability of the TiO2/MIL-100(Fe) composite material - C.A. Rojas-Guerrero; M. Villanueva-Rodríguez; J.L. Guzmán-Mar; A. Hernández-Ramírez; E.I. Cedillo-González; F.E. Longoria Rodríguez; L. Hinojosa-Reyes (Journal of Environmental Chemical Engineering, 2023)

How sweet is too sweet? Measuring sweet taste preferences and liking in familiar and unfamiliar foods amongst Dutch consumers - E.M. Čad; C.S. Tang; M. Mars; K.M. Appleton; K. de Graaf (Food Quality and Preference, 2023)

Heavy metals and metalloids accumulation in common beans (Phaseolus vulgaris L.): A review - M. Silva-Gigante; L. Hinojosa-Reyes; J.M. Rosas-Castor; P.C. Quero-Jiménez; D.A. Pino-Sandoval; J.L. Guzmán-Mar (Chemosphere, 2023)

Counteracting effects of soil biota on emergence and growth of herbaceous plants - Antonio J. Perea; Belén Merelas Meijide; María del Mar Alguacil; Jorge Prieto-Rubio; Concepción Azcón-Aguilar; Julio M. Alcántara; José L. Garrido; Álvaro López-García (Plant and Soil, 2023)
Background Plants condition the biotic composition of their rhizosphere. In turn, this plant legacy on the soil biota may affect the performance of plants recruiting in their vicinity. Unravelling how plant-soil legacies drive plant recruitment is key to understand vegetation dynamics and plant community assembly. Studies on the topic usually focus on the effects of soil microbiota as a whole, while the relative role of different guilds of soil organisms in the plant recruitment processes is not usually dissected. Aims Here, we used soils of Mediterranean woody plant species to test whether arbuscular mycorrhizal fungi (AMF) and small-size microbiota (< 50 µm) (MB) affect the germination success and growth of eight herbaceous plants. Results We documented a significant increase in seedling emergence probability when small-sized MB was present and no effect of AMF. In contrast, the aboveground plant biomass decreased with the presence of MB and increased with that of AMF. Interestingly, those plants growing in the absence of MB and in soils from woody plants associated with higher AMF richness developed higher aboveground biomass. Conclusion This study brings new evidence on how soil microbial communities can determine the performance of their associated herb community, and also, how the effects of different microbial guilds may change across the plant ontogeny. Given these results, the differential effect of soil microbial functional guilds should be considered to better understand plant soil legacies and feedbacks, potentially driving plant recruitment and community assembly.

Exploring sorption of pesticides and PAHs in microplastics derived from plastic mulch films used in modern agriculture - Harshit Sahai; Mar García Valverde; María Murcia Morales; María Dolores Hernando; Ana M. Aguilera del Real; A.R. Fernández- Alba (Chemosphere, 2023)

Study of the cross-talk between Fasciola hepatica juveniles and the intestinal epithelial cells of the host by transcriptomics in an in vitro model - David Becerro-Recio; Judit Serrat; Marta López-García; María Torres-Valle; Francisco Colina; Iván M. Fernández; Javier González-Miguel; Mar Siles-Lucas (Veterinary Parasitology, 2023)

Improving indoor air quality by using photocatalytic paints. Real scale study at the Technical University of Madrid - Antonio Nieto-Márquez; Manuel de Mateo; Andrea Barrios; M. del Mar de la Fuente García-Soto; Adolfo Narros (Atmospheric Pollution Research, 2023)

Evaluating the spread of stony coral tissue loss disease in the Bay Islands, Honduras - Mar Truc; Antonella Rivera; Gabriela M. Ochoa; Damaris Dueñas; Zara Guifarro; Gisselle Brady; Zara Zúniga; Braulio Gutiérrez; Caitlin Chock; Laura Zaldivar (Frontiers in Marine Science, 2023)
Scleractinian corals, considered key reef ecosystem engineers, have suffered irreparable damage over the last decades, with causes widely attributed directly and indirectly to increased human pressure on coral communities. Stony coral tissue loss disease (SCTLD), first detected in Florida in 2014, by early 2023 had spread to 26 jurisdictions in the wider Caribbean, causing severe effects on coral reefs. In January 2020, monitoring efforts to detect SCTLD began on the island of Roatan in Honduras. The disease was first reported in Flowers Bay, Roatan, in September 2020. Since then, dedicated collaborative efforts have been made to assess the severity of the disease, mitigate its effects, and raise coral reef conservation awareness. To track the progression of the outbreak, presence-absence data were collected using the rover diver methodology. With at least 28 species affected, SCTLD has spread across the Bay Islands over a period of 13 months. Roatan and Utila have been the most impacted islands, with the disease encircling them rapidly at a rate of approximately 155 m/day. The spread of SCTLD was overall rapid, but geographical patterns were detected in Roatan, where it showed faster progression on the windward side than on the leeward side. Further research is required to explore whether these disparities are related to marine traffic, water quality, currents, or a combination of multiple factors. Our findings shed new knowledge on the spread of SCTLD in Honduras, which can provide insights for other Caribbean nations whose economies are also dependent on the health of their coral reefs.

Efficient removal of veterinary drugs from aqueous solutions using magnetically separable carbonaceous materials derived from cobalt and iron metal-organic frameworks - Andrea Salazar-García; Sagrario M. Montemayor; Jorge Luis Guzmán-Mar; Bertha A. Puente-Urbina; Gilberto F. Hurtado-López; Laura Hinojosa-Reyes (Environmental Science and Pollution Research, 2023)

Looking behind occlusions: A study on amodal segmentation for robust on-tree apple fruit size estimation - Jordi Gené-Mola; Mar Ferrer-Ferrer; Eduard Gregorio; Pieter M. Blok; Jochen Hemming; Josep-Ramon Morros; Joan R. Rosell-Polo; Verónica Vilaplana; Javier Ruiz-Hidalgo (Computers and Electronics in Agriculture, 2023)

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

An Extensive Comparative Study of Highly Enhanced Pb2+ Adsorption from Synthetic Wastewater by Organically Tailored Silica Aerogels - Faheem Akhter; Abdul Rauf Jamali; Munawar Ali Pinjaro; Abdul Samad Shaikh; Sobhy M. Ibrahim; Maria del Mar Alguacil (Water, Air, & Soil Pollution, 2023)

Applying wind patterns and land use to estimate the concentrations of airborne pollen of herbaceous taxa in a statistical framework - Antonio Picornell; Rocío Ruiz-Mata; Jesús Rojo; Jose Oteros; Marta Recio; Enrique de Gálvez-Montañez; M. Mar Trigo (Urban Climate, 2023)

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Environmental impact analysis of surface printing and 3D inkjet printing applications using an imine based covalent organic framework: A life cycle assessment study - Juan J. Espada; Rosalía Rodríguez; Alejandro de la Peña; Mar Ramos; José L. Segura; Esther M. Sánchez-Carnerero (Journal of Cleaner Production, 2023)

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Corrigendum: Contrasting roles of DOP as a source of phosphorus and energy for marine diazotrophs - Alba Filella; Lasse Riemann; France Van Wambeke; Elvira Pulido-Villena; Angela Vogts; Sophie Bonnet; Olivier Grosso; Julia M. Diaz; Solange Duhamel; Mar Benavides (Frontiers in Marine Science, 2023)

Deep eutectic solvents for improved biomass pretreatment: Current status and future prospective towards sustainable processes - María del Mar Contreras-Gámez; Ángel Galán-Martín; Nalin Seixas; André M. da Costa Lopes; Armando Silvestre; Eulogio Castro (Bioresource Technology, 2023)

Enhanced photocatalytic oxidation of a phenoxyacetic acid herbicide using TiO2–FeOOH/Fe2O3 assisted with sulfate radicals - B. Mendoza-Reyes; S. Mendiola-Alvarez; J. L. Guzmán-Mar; M. Villanueva-Rodríguez; E. J. Ruiz-Ruiz; L. Hinojosa-Reyes (International Journal of Environmental Science and Technology, 2023)

High-resolution variability of dissolved and suspended organic matter in the Cape Verde Frontal Zone - Rubén Campanero; Nadia Burgoa; Bieito Fernández-Castro; Sara Valiente; Mar Nieto-Cid; Alba M. Martínez-Pérez; María Dolores Gelado-Caballero; Nauzet Hernández-Hernández; Ángeles Marrero-Díaz; Francisco Machín; Ángel Rodríguez-Santana; Inés Hernández-García; et al. (Frontiers in Marine Science, 2022)
Distributions of dissolved (DOM) and suspended (POM) organic matter, and their chromophoric (CDOM) and fluorescent (FDOM) fractions, are investigated at high resolution (< 10 km) in the Cape Verde Frontal Zone (CVFZ) during fall 2017. In the epipelagic layer (< 200 m), meso- and submesoscale structures (meanders, eddies) captured by the high resolution sampling dictate the tight coupling between physical and biogeochemical parameters at the front. Remarkably, fluorescent humic-like substances show relatively high fluorescence intensities between 50 and 150 m, apparently not related to local mineralization processes. We hypothesize that it is due to the input of Sahara dust, which transports highly re-worked DOM with distinctive optical properties. In the mesopelagic layer (200-1500 m), our results suggest that DOM and POM mineralization occurs mainly during the transit of the water masses from the formation sites to the CVFZ. Therefore, most of the local mineralization seems to be due to fast-sinking POM produced in situ or imported from the Mauritanian upwelling. These local mineralization processes lead to the production of refractory CDOM, an empirical evidence of the microbial carbon pump mechanism. DOM released from these fast-sinking POM is the likely reason behind the observed columns of relatively high DOC surrounded by areas of lower concentration. DOM and POM dynamics in the CVFZ has turned out to be very complex, in parallel to the complexity of meso- and submesoscale structures present in the area. On top of this high resolution variability, the input of Sahara dust or the release of DOM from sinking particles have been hypothesized to explain the observed distributions.

Global patterns of illegal marine turtle exploitation - Jesse F. Senko; Kayla M. Burgher; Maria del Mar Mancha‐Cisneros; Brendan J. Godley; Irene Kinan‐Kelly; Trevor Fox; Frances Humber; Volker Koch; Andrew T. Smith; Bryan P. Wallace (Global Change Biology, 2022)
Human exploitation of wildlife for food, medicine, curios, aphrodisiacs, and spiritual artifacts represents a mounting 21st‐century conservation challenge. Here, we provide the first global assessment of illegal marine turtle exploitation across multiple spatial scales (i.e., Regional Management Units [RMUs] and countries) by collating data from peer‐reviewed studies, grey literature, archived media reports, and online questionnaires of in‐country experts spanning the past three decades. Based on available information, we estimate that over 1.1 million marine turtles were exploited between 1990 and 2020 against existing laws prohibiting their use in 65 countries or territories and in 44 of the world's 58 marine turtle RMUs, with over 44,000 turtles exploited annually over the past decade. Exploitation across the 30‐year period primarily consisted of green (56%) and hawksbill (39%) turtles when identified by species, with hawksbills (67%) and greens (81%) comprising the majority of turtles exploited in the 1990s and 2000s, respectively, and both species accounting for similar levels of exploitation in the 2010s. Although there were no clear overarching trends in the magnitude or spatial patterns of exploitation across the three decades, there was a 28% decrease in reported exploitation from the 2000s to the 2010s. The 10 RMUs with the highest exploitation in the 2010s included seven green and three hawksbill turtle RMUs, with most reported exploitation occurring in RMUs that typically exhibit a low risk of population decline or loss of genetic diversity. Over the past decade, the number of RMUs with “moderate” or “high” exploitation impact scores decreased. Our assessment suggests that illegal exploitation appears to have declined over the past decade and, with some exceptions, is primarily occurring in large, stable, and genetically diverse marine turtle populations.

First volumetric records of airborne Cladosporium and Alternaria spores in the atmosphere of Al Khor (northern Qatar): a preliminary survey - Dorra Gharbi; Hassan M. Mobayed; Ramzy Mohammed Ali; Amjad Tuffaha; Blessing Reena Dason; Tayseer Ibrahim; Mehdi Adeli; Hisham A. Sattar; Maria del Mar Trigo; Maryam Ali Al-Nesf (Aerobiologia, 2022)
Daily monitoring of airborne fungal spores was carried out for the first time in Al Khor city, Qatar, using a Hirst type 7-day recording volumetric spore trap, from May 2017 to May 2019. During the sampling period, the annual and monthly fluctuations, as well as intradiurnal variations of airborne fungal spore concentrations, were evaluated. Cladosporium, followed by Alternaria, were the spore types most abundant in the atmosphere of the city, with a strong interannual variability in the atmospheric concentrations being observed. The Annual Spore Integrals (ASIns) were 3334 and 1172 spore * day/m 3 (2017–2018), and 6796 and 1538 spore * day/m 3 (2018–2019) for Cladosporium and Alternaria , respectively. Total daily spore concentrations showed significantly positive correlations with mean, minimum, and maximum temperatures but significantly negative correlations with relative humidity. However, due to the scarce rainfalls’ days, we did not find a statistically significant correlations between Cladosporium and Alternaria spore concentrations and this parameter. Despite this, the spore peaks were strongly related to precipitations that occurred during the previous month. In general, no significant correlations were found with wind speed but, regarding wind direction, the higher percentage of spores were collected when wind blows from the 4th quadrant (NW). According to the intradiurnal pattern, Cladosporium fungal spores displayed their maximum daily concentration during 8:00–10:00 h in the morning, with a second peak in the afternoon, while for Alternaria , the maximum peaks were observed between 08:00 and 14:00 h. Because no consistent previous aerobiological studies exist from Qatar, the aim of this study is to define the seasonality and intradiurnal behaviour of these two airborne fungal spore and the role that, in such arid scene, the meteorological parameters play on the spore concentrations.

Contrasting Roles of DOP as a Source of Phosphorus and Energy for Marine Diazotrophs - Alba Filella; Lasse Riemann; France Van Wambeke; Elvira Pulido-Villena; Angela Vogts; Sophie Bonnet; Olivier Grosso; Julia M. Diaz; Solange Duhamel; Mar Benavides (Frontiers in Marine Science, 2022)
The oceanic dissolved organic phosphorus (DOP) pool is mainly composed of P-esters and, to a lesser extent, equally abundant phosphonate and P-anhydride molecules. In phosphate-limited ocean regions, diazotrophs are thought to rely on DOP compounds as an alternative source of phosphorus (P). While both P-esters and phosphonates effectively promote dinitrogen (N 2 ) fixation, the role of P-anhydrides for diazotrophs is unknown. Here we explore the effect of P-anhydrides on N 2 fixation at two stations with contrasting biogeochemical conditions: one located in the Tonga trench volcanic arc region (“volcano,” with low phosphate and high iron concentrations), and the other in the South Pacific Gyre (“gyre,” with moderate phosphate and low iron). We incubated surface seawater with AMP (P-ester), ATP (P-ester and P-anhydride), or 3polyP (P-anhydride) and determined cell-specific N 2 fixation rates, nifH gene abundance, and transcription in Crocosphaera and Trichodesmium . Trichodesmium did not respond to any DOP compounds added, suggesting that they were not P-limited at the volcano station and were outcompeted by the low iron conditions at the gyre station. Conversely, Crocosphaera were numerous at both stations and their specific N 2 fixation rates were stimulated by AMP at the volcano station and slightly by 3polyP at both stations. Heterotrophic bacteria responded to ATP and 3polyP additions similarly at both stations, despite the contrasting phosphate and iron availability. The use of 3polyP by Crocosphaera and heterotrophic bacteria at both low and moderate phosphate concentrations suggests that this compound, in addition to being a source of P, can be used to acquire energy for which both groups compete. P-anhydrides may thus leverage energy restrictions to diazotrophs in the future stratified and nutrient-impoverished ocean.

An alternative approach to estimate any subdaily extreme of rainfall and wind from usually available records - José M. Pérez-Bella; Javier Domínguez-Hernández; Juan E. Martínez-Martínez; Mar Alonso-Martínez; Juan J. del Coz-Díaz (Stochastic Environmental Research and Risk Assessment, 2022)
A wide variety of engineering applications requires the use of maximum values of rainfall intensity and wind speed related to short recording intervals, which can often only be estimated from available less exhaustive records. Given that many locations lack exhaustive climatic records that would allow accurate empirical correlations between different recording intervals to be identified, generic equations are often used to estimate these extreme values. The accuracy of these generic estimates is especially important in fields such as the study of wind-driven rain, in which both climatic variables are combined to characterise the phenomenon. This work assesses the reliability and functionality of some of these most widespread generic equations, analysing climatic datasets gathered since 2008 in 109 weather stations in Spain and the Netherlands. Considering multiple recording intervals at each location, it is verified that most of these generic estimations, used especially in the study of wind-driven rain, have functional limitations and can cause significant errors when characterising both variables for subdaily intervals and extreme conditions. Finally, an alternative approach is proposed to accurately extrapolate extreme values of both variables related to any subdaily recording interval in a functional manner and from any available records.

Nutritional and health beneficial properties of saffron ( Crocus sativus L): a comprehensive review - Tareq Abu-Izneid; Abdur Rauf; Anees Ahmed Khalil; Ahmed Olatunde; Ahood Khalid; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Md. Sahab Uddin; Mojtaba Heydari; Mars Khayrullin; Mohammad Ali Shariati; Adeyemi Oladapo Aremu; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Vertical Niche Partitioning of Archaea and Bacteria Linked to Shifts in Dissolved Organic Matter Quality and Hydrography in North Atlantic Waters - Tamara Rodríguez-Ramos; Mar Nieto-Cid; Adrià Auladell; Elisa Guerrero-Feijóo; Marta M. Varela (Frontiers in Marine Science, 2021)
Understanding the factors that modulate prokaryotic assemblages and their niche partitioning in marine environments is a longstanding challenge in marine microbial ecology. This study analyzes amplicon sequence variant (ASV) diversity and co-occurrence of prokaryotic (Archaea and Bacteria) communities through coastal-oceanic gradients in the NW Iberian upwelling system and adjacent open-ocean (Atlantic Ocean). Biogeographic patterns were investigated in relation with environmental conditions, mainly focusing on the optical signature of the dissolved organic matter (DOM). Alpha- and beta-diversity were horizontally homogeneous [with the only exception of Archaea (∼1700 m depth), attributed to the influence of Mediterranean water, MW], while beta-diversity was significantly vertically stratified. Prokaryotic communities were structured in four clusters (upper subsurface, lower subsurface, intermediate, and deep clusters). Deep (>2000 m) archaeal and bacterial assemblages, and intermediate (500-2000 m) Bacteria (mainly SAR202 and SAR406), were significantly related to humic-like DOM (FDOM-M), while intermediate Archaea were additionally related to biogeochemical attributes of the high-salinity signature of MW. Lower subsurface (100-500 m) Archaea (particularly one ASV belonging to the genus Candidatus Nitrosopelagicus ) were mainly related to the imprint of high-salinity MW, while upper subsurface (≤100 m) archaeal assemblages (particularly some ASVs belonging to Marine Group II) were linked to protein-like DOM (aCDOM254). Conversely, both upper and lower subsurface bacterial assemblages were mainly linked to aCDOM254 (particularly ASVs belonging to Rhodobacteraceae, Cyanobacteria, and Flavobacteriaceae) and nitrite concentration (mainly members of Planctomycetes). Most importantly, our analysis unveiled depth-ecotypes, such as the ASVs MarG.II_1 belonging to the archaeal deep cluster (linked to FDOM-M) and MarG.II_2 belonging to the upper subsurface cluster (related to FDOM-T and aCDOM254). This result strongly suggests DOM-mediated vertical niche differentiation, with further implications for ecosystem functioning. Similarly, positive and negative co-occurrence relationships also suggested niche partitioning (e.g., between the closely related ASVs Thaum._Nit._Nit._Nit._1 and _2) and competitive exclusion (e.g., between Thaum._Nit._Nit._Nit._4 and _5), supporting the finding of non-randomly, vertically structured prokaryotic communities. Overall, differences between Archaea and Bacteria and among closely related ASVs were revealed in their preferential relationship with compositional changes in the DOM pool and environmental forcing. Our results provide new insights on the ecological processes shaping prokaryotic assembly and biogeography.

Evolutionary dynamics of bipartite begomoviruses revealed by complete genome analysis - César A. D. Xavier; Márcio T. Godinho; Talita B. Mar; Camila G. Ferro; Osvaldo F. L. Sande; José C. Silva; Roberto Ramos‐Sobrinho; Renato N. Nascimento; Iraildes Assunção; Gaus S. A. Lima; Alison T. M. Lima; F. Murilo Zerbini (Molecular Ecology, 2021)
Several key evolutionary events marked the evolution of geminiviruses, culminating with the emergence of divided (bipartite) genomes represented by viruses classified in the genus Begomovirus . This genus represents the most abundant group of multipartite viruses, contributing significantly to the observed abundance of multipartite species in the virosphere. Although aspects related to virus‐host interactions and evolutionary dynamics have been extensively studied, the bipartite nature of these viruses has been little explored in evolutionary studies. Here, we performed a parallel evolutionary analysis of the DNA‐A and DNA‐B segments of New World begomoviruses. A total of 239 full‐length DNA‐B sequences obtained in this study, combined with 292 DNA‐A and 76 DNA‐B sequences retrieved from GenBank, were analysed. The results indicate that the DNA‐A and DNA‐B respond differentially to evolutionary processes, with the DNA‐B being more permissive to variation and more prone to recombination than the DNA‐A. Although a clear geographic segregation was observed for both segments, differences in the genetic structure between DNA‐A and DNA‐B were also observed, with cognate segments belonging to distinct genetic clusters. DNA‐B coding regions evolve under the same selection pressures than DNA‐A coding regions. Together, our results indicate an interplay between reassortment and recombination acting at different levels across distinct subpopulations and segments.

The first multi-model ensemble of regional climate simulations at kilometer-scale resolution, part I: evaluation of precipitation - Nikolina Ban; Cécile Caillaud; Erika Coppola; Emanuela Pichelli; Stefan Sobolowski; Marianna Adinolfi; Bodo Ahrens; Antoinette Alias; Ivonne Anders; Sophie Bastin; Danijel Belušić; Ségolène Berthou; et al. (Climate Dynamics, 2021)
Here we present the first multi-model ensemble of regional climate simulations at kilometer-scale horizontal grid spacing over a decade long period. A total of 23 simulations run with a horizontal grid spacing of $$\sim $$ ∼ 3 km, driven by ERA-Interim reanalysis, and performed by 22 European research groups are analysed. Six different regional climate models (RCMs) are represented in the ensemble. The simulations are compared against available high-resolution precipitation observations and coarse resolution ( $$\sim $$ ∼ 12 km) RCMs with parameterized convection. The model simulations and observations are compared with respect to mean precipitation, precipitation intensity and frequency, and heavy precipitation on daily and hourly timescales in different seasons. The results show that kilometer-scale models produce a more realistic representation of precipitation than the coarse resolution RCMs. The most significant improvements are found for heavy precipitation and precipitation frequency on both daily and hourly time scales in the summer season. In general, kilometer-scale models tend to produce more intense precipitation and reduced wet-hour frequency compared to coarse resolution models. On average, the multi-model mean shows a reduction of bias from $$\sim \,$$ ∼ −40% at 12 km to $$\sim \,$$ ∼ −3% at 3 km for heavy hourly precipitation in summer. Furthermore, the uncertainty ranges i.e. the variability between the models for wet hour frequency is reduced by half with the use of kilometer-scale models. Although differences between the model simulations at the kilometer-scale and observations still exist, it is evident that these simulations are superior to the coarse-resolution RCM simulations in the representing precipitation in the present-day climate, and thus offer a promising way forward for investigations of climate and climate change at local to regional scales.

Plasma lipids are associated with white matter microstructural changes and axonal degeneration - Ane Iriondo; Maite García-Sebastian; Arantzazu Arrospide; Maria Arriba; Sara Aurtenetxe; Myriam Barandiaran; Montserrat Clerigue; Mirian Ecay-Torres; Ainara Estanga; Alazne Gabilondo; Andrea Izagirre; Jon Saldias; et al. (Brain Imaging and Behavior, 2021)

The main drivers of methane emissions differ in the growing and flooded fallow seasons in Mediterranean rice fields - Maite Martínez-Eixarch; Carles Alcaraz; Marc Viñas; Joan Noguerol; Xavier Aranda; Frances-Xavier Prenafeta-Boldú; Mar Català-Forner; M. Siobhan Fennessy; Carles Ibáñez (Plant and Soil, 2021)
Purpose To assess 1) the cumulative greenhouse gas emissions –GHG- and global warming potential (methane – CH 4 - and nitrous oxide) from rice fields in the growing and fallow seasons, and 2) the environmental and agronomic drivers of CH 4 emissions, and their relative capacity to explain CH 4 variation. Methods A two-year multisite field experiment covering the agronomic and environmental variability of a rice growing area in NE Iberian Peninsula was conducted with monthly samplings of GHG and monitoring of both environmental and agronomic factors. Information-theoretic framework analysis was used to assess the relative contribution of the environmental and agronomic variables on methane emissions. Results Two thirds of the CH 4 is emitted in the fallow season. Edaphic factors exert more influence during the growing season whereas agronomic factors have a higher impact in the fallow. The implications of these findings on the design of improved mitigation options rice are discussed. Conclusions Soils with higher soil sulphate concentration, bulk density and clay content emit less CH 4 in growing season. In the fallow season, the rates of both straw input and nitrogen fertilization stimulate CH 4 emissions. Graphical abstract

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Feeding habits of Anolis sagrei, an introduced species, in urban ecosystems of Guayas Province - Andrea E. Narváez; Taryn Ghia; M. Mar Moretta-Urdiales; Natalia Molina Moreira (Urban Ecosystems, 2020)

Effects of early life stress on cocaine intake in male and female rhesus macaques - Alison G. P. Wakeford; Brik Kochoian; Erin R. Siebert; Sarah Katznelson; Elyse L. Morin; Brittany R. Howell; Kai M. McCormack; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2020)

Climate and Local Hydrography Underlie Recent Regime Shifts in Plankton Communities off Galicia (NW Spain) - Antonio Bode; Marta Álvarez; Luz María García García; Maria Ángeles Louro; Mar Nieto-Cid; Manuel Ruíz-Villarreal; Marta M. Varela (Oceans, 2020)
A 29-year-long time series (1990–2018) of phyto- and zooplankton abundance and composition is analyzed to uncover regime shifts related to climate and local oceanography variability. At least two major shifts were identified: one between 1997 and 1998, affecting zooplankton group abundance, phytoplankton species assemblages and climatic series, and a second one between 2001 and 2002, affecting microzooplankton group abundance, mesozooplankton species assemblages and local hydrographic series. Upwelling variability was relatively less important than other climatic or local oceanographic variables for the definition of the regimes. Climate-related regimes were influenced by the dominance of cold and dry (1990–1997) vs. warm and wet (1998–2018) periods, and characterized by shifts from low to high life trait diversity in phytoplankton assemblages, and from low to high meroplankton dominance for mesozooplankton. Regimes related to local oceanography were defined by the shift from relatively low (1990–2001) to high (2002–2018) concentrations of nutrients provided by remineralization (or continental inputs) and biological production, and shifts from a low to high abundance of microzooplankton, and from a low to high trait diversity of mesozooplankton species assemblages. These results align with similar shifts described around the same time for most regions of the NE Atlantic. This study points out the different effects of large-scale vs. local environmental variations in shaping plankton assemblages at multiannual time scales.

High fructose-containing drinking water-induced steatohepatitis in rats is prevented by the nicotinamide-mediated modulation of redox homeostasis and NADPH-producing enzymes - S. S. Loza-Medrano; L. A. Baiza-Gutman; L. Manuel-Apolinar; R. García-Macedo; L. Damasio-Santana; O. A. Martínez-Mar; M. C. Sánchez-Becerra; M. Cruz-López; M. A. Ibáñez-Hernández; M. Díaz-Flores (Molecular Biology Reports, 2020)

Risk factors associated with the development of moderate to severe chronic graft-versus-host disease after non-myeloablative conditioning allogeneic stem cell transplantation in patients with AML or MDS - Laurence M. C. Kok; Laura Bungener; Geertruida H. de Bock; Anouschka Biswana; Geertiena van der Wal; Gustaaf W. van Imhoff; Mar Bellido (Human Cell, 2020)
Moderate to severe chronic graft-versus-host disease (cGVHD) is associated with high morbidity, hospital dependency and poor quality of life. In this study, we analyzed a well-defined consecutive series of 98 patients with acute myelogenous leukemia/myelodysplastic syndrome (AML/MDS) who received allogeneic stem cell transplantation with non-myeloablative (NMA) conditioning to determine risk factors associated with the severity of cGVHD. cGVHD was defined according to the 2005 National Institute of Health consensus criteria. Transfusions before transplantation, presence of HLA antibodies, composition of the graft (CD3+, CD19+, CD34+ cells), sibling or matched unrelated donor, female donor to male recipient, CMV serology and the development of acute GVHD (aGVHD), were considered potential risk factors. Multivariate Cox regression analysis identified the number of CD19+ 10 6 /kg (HR 2.79; 95% CI 1.35–5.74), CD3+ 10 6 /kg (HR 2.18; 95% CI 1.04–4.59) infused cells and the presence of patient HLA antibodies before transplantation (HR 2.34; CI 1.11–4.95) as significant risk factors for the development of moderate to severe cGVHD. In summary, we identified in a small, but well-defined cohort, 3 risk factors associated with the severity of cGVHD that should be validated in a larger multi-center study.

Joint representation of connectome-scale structural and functional profiles for identification of consistent cortical landmarks in macaque brain - Shu Zhang; Xi Jiang; Wei Zhang; Tuo Zhang; Hanbo Chen; Yu Zhao; Jinglei Lv; Lei Guo; Brittany R. Howell; Mar M. Sanchez; Xiaoping Hu; Tianming Liu (Brain Imaging and Behavior, 2019)

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

Dopamine D2-like receptor stimulation blocks negative feedback in visual and spatial reversal learning in the rat: behavioural and computational evidence - Johan Alsiö; Benjamin U. Phillips; Júlia Sala-Bayo; Simon R. O. Nilsson; Teresa C. Calafat-Pla; Arazo Rizwand; Jessica M. Plumbridge; Laura López-Cruz; Jeffrey W. Dalley; Rudolf N. Cardinal; Adam C. Mar; Trevor W. Robbins (Psychopharmacology, 2019)

The European Marine Observation and Data Network (EMODnet): Visions and Roles of the Gateway to Marine Data in Europe - Belén Martín Míguez; Antonio Novellino; Matteo Vinci; Simon Claus; Jan-Bart Calewaert; Henry Vallius; Thierry Schmitt; Alessandro Pititto; Alessandra Giorgetti; Natalie Askew; Sissy Iona; Dick Schaap; et al. (Frontiers in Marine Science, 2019)

Compost-assisted phytoremediation of As-polluted soil - Águeda González; Pilar García-Gonzalo; M. Mar Gil-Díaz; Juan Alonso; M. Carmen Lobo (Journal of Soils and Sediments, 2019)

Effective monitoring of freshwater fish - Johannes Radinger; J. Robert Britton; Stephanie M. Carlson; Anne E. Magurran; Juan Diego Alcaraz‐Hernández; Ana Almodóvar; Lluís Benejam; Carlos Fernández‐Delgado; Graciela G. Nicola; Francisco J. Oliva‐Paterna; Mar Torralva; Emili García‐Berthou (Fish and Fisheries, 2019)
Freshwater ecosystems constitute only a small fraction of the planet's water resources, yet support much of its diversity, with freshwater fish accounting for more species than birds, mammals, amphibians or reptiles. Fresh waters are, however, particularly vulnerable to anthropogenic impacts, including habitat loss, climate and land use change, pollution and biological invasions. This environmental degradation, combined with unprecedented rates of biodiversity change, highlights the importance of robust and replicable programmes to monitor freshwater fish. Such monitoring programmes can have diverse aims, including confirming the presence of a single species (e.g., early detection of alien species), tracking changes in the abundance of threatened species, or documenting long‐term temporal changes in entire communities. Irrespective of their motivation, monitoring programmes are only fit for purpose if they have clearly articulated aims and collect data that can meet those aims. This review, therefore, highlights the importance of identifying the key aims in monitoring programmes and outlines the different methods of sampling freshwater fish that can be used to meet these aims. We emphasize that investigators must address issues around sampling design, statistical power, species’ detectability, taxonomy and ethics in their monitoring programmes. Additionally, programmes must ensure that high‐quality monitoring data are properly curated and deposited in repositories that will endure. Through fostering improved practice in freshwater fish monitoring, this review aims to help programmes improve understanding of the processes that shape the Earth's freshwater ecosystems and help protect these systems in face of rapid environmental change.

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Ecological guidelines for designing networks of marine reserves in the unique biophysical environment of the Gulf of California - Adrian Munguia-Vega; Alison L. Green; Alvin N. Suarez-Castillo; Maria Jose Espinosa-Romero; Octavio Aburto-Oropeza; Andrés M. Cisneros-Montemayor; Gabriela Cruz-Piñón; Gustavo Danemann; Alfredo Giron-Nava; Ollin Gonzalez-Cuellar; Cristina Lasch; Maria del Mar Mancha-Cisneros; et al. (Reviews in Fish Biology and Fisheries, 2018)

Structure of gorgonian epifaunal communities in Ecuador (eastern Pacific) - M. Mar Soler-Hurtado; César Megina; Pablo J. López-González (Coral Reefs, 2018)

Algal Colonization of Young Arctic Sea Ice in Spring - Hanna M. Kauko; Lasse M. Olsen; Pedro Duarte; Ilka Peeken; Mats A. Granskog; Geir Johnsen; Mar Fernández-Méndez; Alexey K. Pavlov; Christopher J. Mundy; Philipp Assmy (Frontiers in Marine Science, 2018)

On the significance of the climate-dataset time resolution in characterising wind-driven rain and simultaneous wind pressure. Part I: scalar approach - José M. Pérez-Bella; Javier Domínguez-Hernández; Enrique Cano-Suñén; Juan J. del Coz-Díaz; Mar Alonso-Martínez (Stochastic Environmental Research and Risk Assessment, 2018)

Resist, recover or both? Growth plasticity in response to drought is geographically structured and linked to intraspecific variability in Pinus pinaster - Raúl Sánchez‐Salguero; J. Julio Camarero; Vicente Rozas; Mar Génova; José M. Olano; Alberto Arzac; Antonio Gazol; Leocadia Caminero; Ernesto Tejedor; Martín de Luis; Juan C. Linares (Journal of Biogeography, 2018)
Aim We investigate the effects of the environmental and geographical processes driving growth resilience and recovery in response to drought in Mediterranean Pinus pinaster forests. We explicitly consider how intraspecific variability modulates growth resilience to drought. Location Western Mediterranean basin. Methods We analysed tree rings from a large network of 48 forests (836 trees) encompassing wide ecological and climatic gradients, including six provenances. To characterize the major constraints of P. pinaster growth under extremely dry conditions, we simulated growth responses to temperature and soil moisture using a process‐based growth model coupled with the quantification of climate–growth relationships. Then, we related growth–resilience indices to provenance and site variables considering different drought events. Results Pinus pinaster displayed strong variation in growth resilience across its distributional range, but common patterns were found within each provenance. Post‐drought resilience increased with elevation and drier conditions but decreased with spring precipitation. Trees from dry sites were less resistant to drought but recovered faster than trees from wet sites. Main conclusions Resilience strategies differed among tree provenances: wet forests showed higher growth resistance to drought, while dry forests presented faster growth recovery, suggesting different impacts of climate warming on forest productivity. We detected geographically structured resilience patterns corresponding to different provenances, confirming high intraspecific variability in response to drought. This information should be included in species distribution models to simulate forest responses to climate warming and forecasted aridification.

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Algal Hot Spots in a Changing Arctic Ocean: Sea-Ice Ridges and the Snow-Ice Interface - Mar Fernández-Méndez; Lasse M. Olsen; Hanna M. Kauko; Amelie Meyer; Anja Rösel; Ioanna Merkouriadi; Christopher J. Mundy; Jens K. Ehn; A. Malin Johansson; Penelope M. Wagner; Åse Ervik; Brian K. Sorrell; et al. (Frontiers in Marine Science, 2018)

Salt tolerance of two perennial grass Brachypodium sylvaticum accessions - Nir Sade; Maria del Mar Rubio Wilhelmi; Xiaojuan Ke; Yariv Brotman; Matthew Wright; Imran Khan; Wagner De Souza; Elias Bassil; Christian M. Tobias; Roger Thilmony; John P. Vogel; Eduardo Blumwald (Plant Molecular Biology, 2018)

Transcriptomics in the wild: Hibernation physiology in free‐ranging dwarf lemurs - Sheena L. Faherty; José Luis Villanueva‐Cañas; Marina B. Blanco; M. Mar Albà; Anne D. Yoder (Molecular Ecology, 2018)
Hibernation is an adaptive strategy some mammals use to survive highly seasonal or unpredictable environments. We present the first investigation on the transcriptomics of hibernation in a natural population of primate hibernators: Crossley's dwarf lemurs ( Cheirogaleus crossleyi ). Using capture–mark–recapture techniques to track the same animals over a period of 7 months in Madagascar, we used RNA‐seq to compare gene expression profiles in white adipose tissue (WAT) during three distinct physiological states. We focus on pathway analysis to assess the biological significance of transcriptional changes in dwarf lemur WAT and, by comparing and contrasting what is known in other model hibernating species, contribute to a broader understanding of genomic contributions of hibernation across Mammalia. The hibernation signature is characterized by a suppression of lipid biosynthesis, pyruvate metabolism and mitochondrial‐associated functions, and an accumulation of transcripts encoding ribosomal components and iron‐storage proteins. The data support a key role of pyruvate dehydrogenase kinase isoenzyme 4 ( PDK4 ) in regulating the shift in fuel economy during periods of severe food deprivation. This pattern of PDK4 holds true across representative hibernating species from disparate mammalian groups, suggesting that the genetic underpinnings of hibernation may be ancestral to mammals.

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

100 Days of marine Synechococcus – Ruegeria pomeroyi interaction: A detailed analysis of the exoproteome - Amandeep Kaur; Juan R. Hernandez‐Fernaud; Maria del Mar Aguilo‐Ferretjans; Elizabeth M. Wellington; Joseph A. Christie‐Oleza (Environmental Microbiology, 2018)
Summary Marine phototroph and heterotroph interactions are vital in maintaining the nutrient balance in the oceans as essential nutrients need to be rapidly cycled before sinking to aphotic layers. The aim of this study was to highlight the molecular mechanisms that drive these interactions. For this, we generated a detailed exoproteomic time‐course analysis of a 100‐day co‐culture between the model marine picocyanobacterium Synechococcus sp. WH7803 and the Roseobacter strain Ruegeria pomeroyi DSS‐3, both in nutrient‐enriched and natural oligotrophic seawater. The proteomic data showed a transition between the initial growth phase and stable‐state phase that, in the case of the heterotroph, was caused by a switch in motility attributed to organic matter availability. The phototroph adapted to seawater oligotrophy by reducing its selective leakiness, increasing the acquisition of essential nutrients and secreting conserved proteins of unknown function. We also report a surprisingly high abundance of extracellular superoxide dismutase produced by Synechococcus and a dynamic secretion of potential hydrolytic enzyme candidates used by the heterotroph to cleave organic groups and hydrolase polymeric organic matter produced by the cyanobacterium. The time course dataset we present here will become a reference for understanding the molecular processes underpinning marine phototroph‐heterotroph interactions.

Impact of Cr and Zn on Growth, Biochemical and Physiological Parameters, and Metal Accumulation by Wheat and Barley Plants - Agueda González; M. Mar Gil-Díaz; Paloma Pinilla; M. Carmen Lobo (Water, Air, & Soil Pollution, 2017)

Crustacean zooplankton release copious amounts of dissolved organic matter as taurine in the ocean - Elisabeth L. Clifford; Dennis A. Hansell; Marta M. Varela; Mar Nieto‐Cid; Gerhard J. Herndl; Eva Sintes (Limnology and Oceanography, 2017)
Taurine (Tau), an amino acid‐like compound, is present in almost all marine metazoans including crustacean zooplankton. It plays an important physiological role in these organisms and is released into the ambient water throughout their life cycle. However, limited information is available on the release rates by marine organisms, the concentrations and turnover of Tau in the ocean. We determined dissolved free Tau concentrations throughout the water column and its release by abundant crustacean mesozooplankton at two open ocean sites (Gulf of Alaska and North Atlantic). At both locations, the concentrations of dissolved free Tau were in the low nM range (up to 15.7 nM) in epipelagic waters, declining sharply in the mesopelagic to about 0.2 nM and remaining fairly stable throughout the bathypelagic waters. Pacific amphipod–copepod assemblages exhibited lower dissolved free Tau release rates per unit biomass (0.8 ± 0.4 μmol g −1 C‐biomass h −1 ) than Atlantic copepods (ranging between 1.3 ± 0.4 μmol g −1 C‐biomass h −1 and 9.5 ± 2.1 μmol g −1 C‐biomass h −1 ), in agreement with the well‐documented inverse relationship between biomass‐normalized excretion rates and body size. Our results indicate that crustacean zooplankton might contribute significantly to the dissolved organic matter flux in marine ecosystems via dissolved free Tau release. Based on the release rates and assuming steady state dissolved free Tau concentrations, turnover times of dissolved free Tau range from 0.05 d to 2.3 d in the upper water column and are therefore similar to those of dissolved free amino acids. This rapid turnover indicates that dissolved free Tau is efficiently consumed in oceanic waters, most likely by heterotrophic bacteria.

MAM-E17 rat model impairments on a novel continuous performance task: effects of potential cognitive enhancing drugs - Adam C. Mar; Simon R. O. Nilsson; Begoña Gamallo-Lana; Ming Lei; Theda Dourado; Johan Alsiö; Lisa M. Saksida; Timothy J. Bussey; Trevor W. Robbins (Psychopharmacology, 2017)

Individual attributes and party affect large carnivore attacks on humans - Pedro José Garrote; María del Mar Delgado; José Vicente López-Bao; José M. Fedriani; Giulia Bombieri; Vincenzo Penteriani (European Journal of Wildlife Research, 2017)

Neurological involvement in patients with acute/recent HIV-1 infection. A case-control study - Juan Ambrosioni; Francisca Artigues; David Nicolás; Judit Peñafiel; Fernando Agüero; Christian Manzardo; María Mar Mosquera; Sonsoles Sánchez-Palomino; Elisa De Lazzari; María A. Marcos; Montserrat Plana; José M. Miró (Journal of NeuroVirology, 2017)

Changes in the Mediterranean pine forest: pollination patterns and annual trends of airborne pollen - Concepción De Linares; Rosario Delgado; Maria Jesús Aira; Purificación Alcázar; Silvia Alonso-Pérez; Marzia Boi; Paloma Cariñanos; Emilio Cuevas; Consuelo Díaz de la Guardia; Belén Elvira-Rendueles; Delia Fernández-González; Carmen Galán; et al. (Aerobiologia, 2017)

Recent debris flows in the Portainé catchment (Eastern Pyrenees, Spain): analysis of monitoring and field data focussing on the 2015 event - Rosa M. Palau; Marcel Hürlimann; Jordi Pinyol; José Moya; Ane Victoriano; Mar Génova; Càrol Puig-Polo (Landslides, 2017)

Volume 30 Issue 02 View Issue TOC Volume 30, No. 2 Satellites to Seafloor: Toward Fully Autonomous Ocean Sampling - Andrew Thompson; Yi Chao; Steve Chien; James Kinsey; M. Mar Flexas; Zachary Erickson; John Farrara; David Fratantoni; Andrew Branch; Selina Chu; Martina Troesch; Brian Claus; et al. (Oceanography, 2017)

Compatibility of sulfoxaflor and other modern pesticides with adults of the predatory mite Amblyseius swirskii. Residual contact and persistence studies - M. Mar Fernández; Pilar Medina; Andrea Wanumen; Pedro Del Estal; Guy Smagghe; Elisa Viñuela (BioControl, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Can mixtures of horizontally and vertically transmitted nucleopolyhedrovirus genotypes be effective for biological control of Spodoptera exigua? - Cristina Virto; Trevor Williams; David Navarro; M. Mar Tellez; Rosa Murillo; Primitivo Caballero (Journal of Pest Science, 2017)

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

Erratum to: The continuous performance test (rCPT) for mice: a novel operant touchscreen test of attentional function - Chi Hun Kim; Martha Hvoslef-Eide; Simon R. O. Nilsson; Mark R. Johnson; Bronwen R. Herbert; Trevor W. Robbins; Lisa M. Saksida; Timothy J. Bussey; Adam C. Mar (Psychopharmacology, 2016)

Inhibitory Injury Signaling Represses Axon Regeneration After Dorsal Root Injury - Fernando M. Mar; Anabel R. Simões; Inês S. Rodrigo; Mónica M. Sousa (Molecular Neurobiology, 2016)

Myelin Lipids Inhibit Axon Regeneration Following Spinal Cord Injury: a Novel Perspective for Therapy - Fernando M. Mar; Tiago F. da Silva; Marlene M. Morgado; Lorena G. Rodrigues; Daniel Rodrigues; Marta I. L. Pereira; Ana Marques; Vera F. Sousa; João Coentro; Clara Sá-Miranda; Mónica M. Sousa; Pedro Brites (Molecular Neurobiology, 2016)

Microbially-Mediated Fluorescent Organic Matter Transformations in the Deep Ocean. Do the Chemical Precursors Matter? - Fran L. Aparicio; Mar Nieto-Cid; Encarna Borrull; Estela Romero; Colin A. Stedmon; Maria M. Sala; Josep M. Gasol; Aida F. Ríos; Cèlia Marrasé (Frontiers in Marine Science, 2015)

The continuous performance test (rCPT) for mice: a novel operant touchscreen test of attentional function - Chi Hun Kim; Martha Hvoslef-Eide; Simon R. O. Nilsson; Mark R. Johnson; Bronwen R. Herbert; Trevor W. Robbins; Lisa M. Saksida; Timothy J. Bussey; Adam C. Mar (Psychopharmacology, 2015)

A novel 2- and 3-choice touchscreen-based continuous trial-unique nonmatching-to-location task (cTUNL) sensitive to functional differences between dentate gyrus and CA3 subregions of the hippocampus - C. A. Oomen; M. Hvoslef-Eide; D. Kofink; F. Preusser; A. C. Mar; L. M. Saksida; T. J. Bussey (Psychopharmacology, 2015)

The NEWMEDS rodent touchscreen test battery for cognition relevant to schizophrenia - M. Hvoslef-Eide; A. C. Mar; S. R. O. Nilsson; J. Alsiö; C. J. Heath; L. M. Saksida; T. W. Robbins; T. J. Bussey (Psychopharmacology, 2015)

Comparing the effects of subchronic phencyclidine and medial prefrontal cortex dysfunction on cognitive tests relevant to schizophrenia - K. A. L. McAllister; A. C. Mar; D. E. Theobald; L. M. Saksida; T. J. Bussey (Psychopharmacology, 2015)

Trial-unique, delayed nonmatching-to-location (TUNL) touchscreen testing for mice: sensitivity to dorsal hippocampal dysfunction - Chi Hun Kim; Carola Romberg; Martha Hvoslef-Eide; Charlotte A. Oomen; Adam C. Mar; Christopher J. Heath; Andrée-Anne Berthiaume; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

The role of 5-HT2C receptors in touchscreen visual reversal learning in the rat: a cross-site study - J. Alsiö; S. R. O. Nilsson; F. Gastambide; R. A. H. Wang; S. A. Dam; A. C. Mar; M. Tricklebank; T. W. Robbins (Psychopharmacology, 2015)

Structural characterization of amphiphilic siderophores produced by a soda lake isolate, Halomonas sp. SL01, reveals cysteine-, phenylalanine- and proline-containing head groups - Luis O’mar Serrano Figueroa; Benjamin Schwarz; Abigail M. Richards (Extremophiles, 2015)

European policy responses to climate change: progress on mainstreaming emissions reduction and adaptation - Frans Berkhout; Laurens M. Bouwer; Joanne Bayer; Maha Bouzid; Mar Cabeza; Susanne Hanger; Andries Hof; Paul Hunter; Laura Meller; Anthony Patt; Benjamin Pfluger; Tim Rayner; et al. (Regional Environmental Change, 2015)

Airborne pollen of Olea europaea L. in Tetouan (NW Morocco): heat requirements and forecasts - Lamiaa Achmakh; Hassan Bouziane; Nadia Aboulaich; M. Mar Trigo; Asmae Janati; Mohamed Kadiri (Aerobiologia, 2015)

Mating type and spore killing characterization of Fusarium verticillioides strains - Li Guo; Adam Z. Blatt; David M. Geiser; Maria del Mar Jiménez-Gasco; Gretchen A. Kuldau (Mycological Progress, 2015)

Susac-Like Syndrome in a Chronic Cocaine Abuser: Could Levamisole Play a Role? - P. Hantson; V. Di Fazio; M. Del Mar Ramirez Fernandez; N. Samyn; T. Duprez; V. van Pesch (Journal of Medical Toxicology, 2015)

Deep sequencing of the olfactory epithelium reveals specific chemosensory receptors are expressed at sexual maturity in the E uropean eel A nguilla anguilla - Allison M. Churcher; Peter C. Hubbard; João Pedro Marques; Adelino V. M. Canário; Mar Huertas (Molecular Ecology, 2015)
Vertebrate genomes encode a diversity of G protein‐coupled receptor ( GPCR ) that belong to large gene families and are used by olfactory systems to detect chemical cues found in the environment. It is not clear however, if individual receptors from these large gene families have evolved roles that are specific to certain life stages. Here, we used deep sequencing to identify differentially expressed receptor transcripts in the olfactory epithelia ( OE ) of freshwater, seawater and sexually mature male eels ( Anguilla anguilla ). This species is particularly intriguing because of its complex life cycle, extreme long‐distance migrations and early‐branching position within the teleost phylogeny. In the A. anguilla OE , we identified full‐length transcripts for 13, 112, 6 and 38 trace amine‐associated receptors, odorant receptors ( OR ) and type I and type II vomeronasal receptors (V1R and V2R). Most of these receptors were expressed at similar levels at different life stages and a subset of OR and V2R‐like transcripts was more abundant in sexually mature males suggesting that OR s and V2R‐like genes are important for reproduction. We also identified a set of GPCR signal transduction genes that were differentially expressed indicating that eels make use of different GPCR signal transduction genes at different life stages. The finding that a diversity of chemosensory receptors is expressed in the olfactory epithelium and that a subset is differentially expressed suggests that most receptors belonging to large chemosensory gene families have functions that are important at multiple life stages, while a subset has evolved specific functions at different life stages.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Event-Related Spectral EEG Power on Presentation of Pseudowords and Words of the “Animate” and “Inanimate” Categories - V. M. Verkhlyutov; I. V. Mar’ina; V. B. Strelets (Neuroscience and Behavioral Physiology, 2014)

Urokinase Plasminogen Activator System in Synovial Fibroblasts from Osteoarthritis Patients: Modulation by Inflammatory Mediators and Neuropeptides - Selene Pérez-García; Mar Carrión; Rebeca Jimeno; Ana M. Ortiz; Isidoro González-Álvaro; Julián Fernández; Rosa P. Gomariz; Yasmina Juarranz (Journal of Molecular Neuroscience, 2014)

Segregation and associations of enological and agronomic traits in Graciano × Tempranillo wine grape progeny (Vitis vinifera L.) - Shiren Song; María del Mar Hernández; Ignacio Provedo; Cristina M. Menéndez (Euphytica, 2014)

Divergent effects of D2/3 receptor activation in the nucleus accumbens core and shell on impulsivity and locomotor activity in high and low impulsive rats - M. Moreno; D. Economidou; A. C. Mar; C. López-Granero; D. Caprioli; D. E. Theobald; A. Fernando; A. H. Newman; T. W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2013)

Effect of meteorological parameters on Poaceae pollen in the atmosphere of Tetouan (NW Morocco) - Nadia Aboulaich; Lamiaa Achmakh; Hassan Bouziane; M. Mar Trigo; Marta Recio; Mohamed Kadiri; Baltasar Cabezudo; Hassane Riadi; Mohamed Kazzaz (International Journal of Biometeorology, 2013)

The F-Actin Cortex in Chromaffin Granule Dynamics and Fusion: a Minireview - José Villanueva; Cristina J. Torregrosa-Hetland; Virginia García-Martínez; María del Mar Francés; Salvador Viniegra; Luis M. Gutiérrez (Journal of Molecular Neuroscience, 2012)

Quantitative structure-activity relationship study and directed synthesis of Thieno[2,3-d]pyrimidine-2,4-diones as monocarboxylate transporter 1 inhibitors - O. T. Devinyak; Mikh. V. Slivka; Mar. V. Slivka; V. M. Vais; V. G. Lendel (Medicinal Chemistry Research, 2012)

The effects of drying on sediment nitrogen content in a Mediterranean intermittent stream: a microcosms study - Rosa Gómez; M. Isabel Arce; J. Javier Sánchez; M. del Mar Sánchez-Montoya (Hydrobiologia, 2012)

Tyrosine phosphorylation turns alkaline transition into a biologically relevant process and makes human cytochrome c behave as an anti-apoptotic switch - José M. García-Heredia; Antonio Díaz-Quintana; Maria Salzano; Mar Orzáez; Enrique Pérez-Payá; Miguel Teixeira; Miguel A. De la Rosa; Irene Díaz-Moreno (JBIC Journal of Biological Inorganic Chemistry, 2011)

Do seasonal changes in habitat features influence aquatic macroinvertebrate assemblages in perennial versus temporary Mediterranean streams? - Eduardo M. García-Roger; M. del Mar Sánchez-Montoya; Rosa Gómez; M. Luisa Suárez; M. Rosario Vidal-Abarca; Jérôme Latron; Maria Rieradevall; Narcís Prat (Aquatic Sciences, 2011)

About the role of CK2 in plant signal transduction - Jordi Moreno-Romero; Laia Armengot; M. Mar Marquès-Bueno; Marcela Cadavid-Ordóñez; M. Carmen Martínez (Molecular and Cellular Biochemistry, 2011)

Characterization of root-nodulating bacteria associated to Prosopis farcta growing in the arid regions of Tunisia - A. Fterich; M. Mahdhi; M. A. Caviedes; E. Pajuelo; R. Rivas; I. D. Rodriguez-Llorente; M. Mars (Archives of Microbiology, 2011)

Ontogeny of the conus papillaris of the lizard Gallotia galloti and cellular response following transection of the optic nerve: an immunohistochemical and ultrastructural study - M. C. Alfayate; E. Santos; C. Yanes; N. Casañas; R. Viñoly; Maria del Mar Romero-Alemán; Maximina Monzón-Mayor (Cell and Tissue Research, 2011)

Development and characterization of SSR markers for pomegranate (Punica granatum L.) using an enriched library - N. Hasnaoui; A. Buonamici; F. Sebastiani; M. Mars; M. Trifi; G. G. Vendramin (Conservation Genetics Resources, 2010)

Cytokine and hormone responses to resistance training - Mikel Izquierdo; Javier Ibañez; Jose A. L. Calbet; Ion Navarro-Amezqueta; Miriam González-Izal; Fernando Idoate; Keijo Häkkinen; William J. Kraemer; Mercedes Palacios-Sarrasqueta; Mar Almar; Esteban M. Gorostiaga (European Journal of Applied Physiology, 2009)

The effect of recent climatic trends on Urticaceae pollination in two bioclimatically different areas in the Iberian Peninsula: Malaga and Vigo - Marta Recio; F. Javier Rodríguez-Rajo; M. Victoria Jato; M. Mar Trigo; Baltasar Cabezudo (Climatic Change, 2009)

Dissociable effects of noradrenaline, dopamine, and serotonin uptake blockade on stop task performance in rats - Andrea Bari; Dawn M. Eagle; Adam C. Mar; Emma S. J. Robinson; Trevor W. Robbins (Psychopharmacology, 2009)

Natural nodulation of five wild legumes in the south of Tunisia - M. Rejili; M. Mahdhi†; A. Ferchichi; M. Mars (Plant Biosystems, 2009)

Dynamics of the hydrocarbon‐degrading Cycloclasticus bacteria during mesocosm‐simulated oil spills - Eva Teira; Itziar Lekunberri; Josep M. Gasol; Mar Nieto‐Cid; Xosé Antón Álvarez‐Salgado; Francisco G. Figueiras (Environmental Microbiology, 2007)
Summary We used catalysed reported deposition – fluorescence in situ hybridization (CARD‐FISH) to analyse changes in the abundance of the bacterial groups Alphaproteobacteria , Gammaproteobacteria and Bacteroidetes, and of hydrocarbon‐degrading Cycloclasticus bacteria in mesocosms that had received polycyclic aromatic hydrocarbons (PAHs) additions. The effects of PAHs were assessed under four contrasting hydrographic conditions in the coastal upwelling system of the Rías Baixas: winter mixing, spring bloom, summer stratification and autumn upwelling. We used realistic additions of water soluble PAHs (approximately 20–30 μg l −1 equivalent of chrysene), but during the winter period we also investigated the effect of higher PAHs concentrations (10–80 μg l −1 chrysene) on the bacterial community using microcosms. The most significant change observed was a significant reduction (68 ± 5%) in the relative abundance of Alphaproteobacteria . The magnitude of the response of Cycloclasticus bacteria (positive with probe CYPU829) to PAHs additions varied depending on the initial environmental conditions, and on the initial concentration of added PAHs. Our results clearly show that bacteria of the C ycloclasticus group play a major role in low molecular weight PAHs biodegradation in this planktonic ecosystem. Their response was stronger in colder waters, when their background abundance was also higher. During the warm periods, the response of Cycloclasticus was limited, possibly due to both, a lower bioavailability of PAHs caused by abiotic factors (solar radiation, temperature), and by inorganic nutrient limitation of bacterial growth.

Risk of pollen allergy in Nerja (southern Spain): a pollen calendar - Silvia Docampo; Marta Recio; M. Mar Trigo; Marta Melgar; Baltasar Cabezudo (Aerobiologia, 2007)

Escherichia coli has multiple enzymes that attack TNT and release nitrogen for growth - M. Mar González‐Pérez; Pieter Van Dillewijn; Rolf‐M. Wittich; Juan L. Ramos (Environmental Microbiology, 2007)
Summary There has been a growing interest in the degradation of 2,4,6‐trinitrotoluene (TNT) over the last decade, ever since its removal from polluted sites was declared an international environmental priority. Certain aerobic and anaerobic microorganisms are capable of using TNT as an N source, although very few studies have proven the mineralization of this compound. An unexpected observation in our laboratory led us to discover that certain Escherichia coli bench laboratory strains have multiple enzymes that attack TNT. One of the NemA products is responsible for the release of nitrite from the nitroaromatic ring: among the metabolites observed in vitro include Meisenheimer dihydride complexes of TNT from which 2‐hydroxylamino‐6‐nitrotoluene is slowly formed during their rearomatization under concomitant release of nitrite. Furthermore, NemA, together with NfsA and NfsB reduce the nitro groups on the aromatic ring to the corresponding hydroxylamino derivatives, which probably results in the release of ammonium ions which can, in turn be used as a nitrogen source by E. coli for growth.

Formulation of a dry powder influenza vaccine for nasal delivery - Robert J. Garmise; Kevin Mar; Timothy M. Crowder; C. Robin Hwang; Matthew Ferriter; Juan Huang; John A. Mikszta; Vincent J. Sullivan; Anthony J. Hickey (AAPS PharmSciTech, 2006)

FISH analysis of hematological neoplasias with 1p36 rearrangements allows the definition of a cluster of 2.5Mb included in the minimal region deleted in 1p36 deletion syndrome - Idoya Lahortiga; Iria Vzquez; Elena Belloni; Jos P. Romn; Patrizia Gasparini; Francisco J. Novo; Isabel Zudaire; Pier G. Pelicci; Jess M. Hernndez; Mara J. Calasanz; Mara D. Odero (Human Genetics, 2005)

H2O2-induced changes in mitochondrial activity in isolated mouse pancreatic acinar cells - Antonio Gonzlez; Mara P. Granados; Gins M. Salido; Jos A. Pariente (Molecular and Cellular Biochemistry, 2005)

Effects of nefazodone on the development of experimentally induced tumors in stressed rodents - Manuel Freire-Garabal; Manuel Rey-Mndez; Luis A. Garca-Vallejo; Jos Balboa; Jos M. Surez; Elena Rodrigo; Julio Brenlla; Mara J. Nez (Psychopharmacology, 2004)

Salt-dependent studies of NADP-dependent isocitrate dehydrogenase from the halophilic archaeon Haloferax volcanii - Dominique Madern; Mnica Camacho; Adoracin Rodrguez-Arnedo; Mara-Jos Bonete; Giuseppe Zaccai (Extremophiles, 2004)

Occurrence and Distribution of Pesticides in the Province of Bologna, Italy, Using Honeybees as Bioindicators - S. Ghini; M. Fernndez; Y. Pic; R. Marn; F. Fini; J. Maes; S. Girotti (Archives of Environmental Contamination and Toxicology, 2004)

OMNIITOX - operational life-cycle impact assessment models and information tools for practitioners - Sverker Molander; Peter Lidholm; Diederik Schowanek; Mar Recasens; Pere Fullana i Palmer; Frans M. Christensen; Jeroen B. Guinee; Michael Hauschild; Olivier Jolliet; David W. Pennington; Raul Carlson; Till M. Bachmann (The International Journal of Life Cycle Assessment, 2004)

Lead in Feathers and ?-Aminolevulinic Acid Dehydratase Activity in Three Raptor Species from an Unpolluted Mediterranean Forest (Southeastern Spain) - E. Martnez-Lpez; J. E. Martnez; P. Mara-Mojica; J. Pealver; M. Pulido; J. F. Calvo; A. J. Garca-Fernndez (Archives of Environmental Contamination and Toxicology, 2004)

Denitrification from an irrigated soil fertilized with pig slurry under Mediterranean conditions - Antonio Vallejo; Jos A. Dez; Lus M. Lpez-Valdivia; Mara C. Cartagena; Ana Tarquis; Pedro Herniz (Biology and Fertility of Soils, 2004)

FUSARIUM-ID v. 1.0: A DNA Sequence Database for Identifying Fusarium - David M. Geiser; María del Mar Jiménez-Gasco; Seogchan Kang; Izabela Makalowska; Narayanan Veeraraghavan; Todd J. Ward; Ning Zhang; Gretchen A. Kuldau; Kerry O'donnell (European Journal of Plant Pathology, 2004)

The impact of dnaKJ overexpression on recombinant protein solubility results from antagonistic effects on the control of protein quality - Lisa Petersson; M. Mar Carrió; Andrea Vera; Antonio Villaverde (Biotechnology Letters, 2004)

Effect of chronic accumulation of aluminum on renal function, cortical renal oxidative stress and cortical renal organic anion transport in rats - Stella T. Mahieu; Marisa Gionotti; Nstor Millen; Mara Mnica Elas (Archives of Toxicology, 2003)

Protein aggregation in recombinant bacteria: biological role of inclusion bodies - Antonio Villaverde; M. Mar Carrió (Biotechnology Letters, 2003)

Biodegradation of sunflower hulls with different nitrogen sources under mesophilic and thermophilic incubations - Mara M. Conghos; Mara E. Aguirre; Ral M. Santamara (Biology and Fertility of Soils, 2003)

Cleared extrachromosomal domain (CED): a nuclear domain enriched in nuclear matrix filaments is a common structure in sturgeon podocytes - Jos M. Icardo; Jos L. Ojeda; Mara T. Berciano; Alberto Domezain; Miguel Lafarga (Histochemistry and Cell Biology, 2002)

Identification of Pathogenic Races 0, 1B/C, 5, And 6 Of Fusarium Oxysporum F. Sp. Ciceris With Random Amplified Polymorphic DNA (RAPD) - María del Mar Jiménez-Gasco; Encarnación Pérez-Artés; Rafael M. Jiménez-Diaz (European Journal of Plant Pathology, 2001)

Genomic organization of the human CD5 gene - Olga Padilla; Javier Calvo; Josep Maria Vil; Mnica Arman; Idoia Gimferrer; Lourdes Places; Mara Teresa Arias; Miguel Angel Pujana; Jordi Vives; Francisco Lozano (Immunogenetics, 2000)

Biodegradation, plasmid‐encoded catabolic pathways, host factors and cell metabolism - Silvia Marqués; Maxi Manzanera; M. Mar González‐Pérez; Raquel Ruíz; Juan Ramos (Environmental Microbiology, 1999)

Genotypic diversity and symbiotic effectiveness of rhizobia isolated from root nodules of Phaseolus vulgaris L. grown in Tunisian soils - R. Mhamdi; M. Jebara; M. E. Aouani; R. Ghrir; M. Mars (Biology and Fertility of Soils, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Effect of river regulation on the life‐history patterns of Barbus sclateri in the Segura river basin (south‐east Spain) - M. Del Mar Torralva; M. Angeles Puig; C. Fernández‐delgado (Journal of Fish Biology, 1997)
The age structure, growth and reproduction of Barbus sclateri in a non‐regulated section of the Segura River were similar to previously studied populations of undisturbed areas. Differences in the duration of the growth period or the reproductive cycle are considered evidence of the plasticity of the species as it adapts to different latitudes and local habitat characteristics. However, this population differed from one in a section with artificial water flow regulation. The non‐regulated river population had a greater number of age groups, displayed a regular condition cycle, reached maturity earlier at lower ages and lengths and showed greater fecundity than the regulated river population. The mean lengths at age were longer in the regulated river population, possibly owing to the longer river section studied and/or to selective mortality of smaller specimens within a particular age group from the high water velocity when sluices are opened.

Evaluation of fluorometric and zymographic methods as activity assays for stromelysins and gelatinases - Ana R. Quesada; M. Mar Barbacid; Emilia Mira; Piedad Fernandez-Resa; Gabriel Marquez; Miguel Aracil (Clinical & Experimental Metastasis, 1997)

Metabolism of acetaldehyde and Custers effect in the yeast - J. M. Carrascosa; Mara Dolores Viguera; I. Nez de Castro; W. A. Scheffers (Antonie van Leeuwenhoek, 1981)

Biochemical characterization of a red cell UMP kinase variant found in the Warao Indians of Venezuela - Mara L. Gallango; A. Mller; R. Suinaga (Biochemical Genetics, 1978)

Extracellular ?-lactamase from Escherichia coli - Jos M. Tanco; Mara del Pilar Miravalles; Jos M. Arcos (Archives of Microbiology, 1970)

Vaccination contre la rougeole en milieu coutumier sngalais par le vaccin vivant attnu Edmonston B - M. Rey; R. Baylet; I. Diop Mar; P. Cantrelle (Archives of Virology, 1965)